Manufacturing method of optical laminate

The method for manufacturing optical laminates with a low-tensile modulus protective film ensures precise optical axis alignment, addressing the need for higher quality and yield in advanced image display devices.

JP2025003180AActive Publication Date: 2025-01-09NITTO DENKO CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2023103710
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-23
Publication Date
2025-01-09
Estimated Expiration
2043-06-23

AI Technical Summary

Technical Problem

Existing optical laminates for image display devices, particularly those used in VR goggles, require higher precision in aligning optical axes and improved quality to meet the demands of advanced applications.

Method used

A method for manufacturing an optical laminate involving a base material, an absorption type polarizing film, and a protective film, where the protective film has a lower tensile modulus than the base material, allowing precise alignment of optical axes by peeling off the protective film without damaging the polarizing film, and using self-adhesive films to prevent residue and enhance workability.

Benefits of technology

The method enables the production of high-quality optical laminates with improved yield and precise optical axis alignment, suitable for advanced image display devices like VR goggles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025003180000001_ABST
    Figure 2025003180000001_ABST
Patent Text Reader

Abstract

To provide an optical laminate with high quality at a high yield.SOLUTION: A manufacturing method of an optical laminate includes: preparing a first laminate 100 having a base material 53, an absorption type polarization film 28 formed on the base material 53, and a protective film 54 bonded to the absorption type polarization film 28; cutting the first laminate 100 into a prescribed shape to obtain a leaf-like first laminate 100; preparing a leaf-like second laminate 200 having a retardation member 30 having a first principal surface 30a and a second principal surface 30b facing each other and a first adhesive layer 41 arranged on the retardation member 30 side of the first principal surface 30a; and peeling the protective film 54 from the leaf-like first laminate 100 and bonding the absorption type polarization film 28 of the leaf-like first laminate 100 to the first adhesive layer 41 of the leaf-like second laminate 200. The absorption type polarization film 28 has a thickness of 7 μm or less and the protective film 54 has a tensile elastic modulus smaller than that of the base material 53.SELECTED DRAWING: Figure 1C
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing an optical laminate. [Background technology]

[0002] Image display devices, such as liquid crystal display devices and electroluminescence (EL) display devices (e.g., organic EL display devices), are rapidly becoming widespread. In image display devices, optical members such as retardation members and polarizing members are generally used to realize image display and improve image display performance (see, for example, Patent Document 1). These optical members can be integrated in advance and mounted on the image display device as an optical laminate.

[0003] In recent years, new applications for image display devices have been developed. For example, goggles with displays (VR goggles) for realizing Virtual Reality (VR) have started to be commercialized. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2021-103286 A Summary of the Invention [Problem to be solved by the invention]

[0005] As the applications of image display devices expand, there are cases where higher quality than before is required for the optical laminate including the optical member. For example, there are cases where it is desired that the optical axes of the optical members included in the optical laminate be adjusted with high precision.

[0006] In view of the above, a main object of the present invention is to provide a high-quality optical laminate with a high yield. [Means for solving the problem]

[0007] 1. A method for producing an optical laminate according to an embodiment of the present invention includes: preparing a first laminate having a substrate, an absorptive polarizing film formed on the substrate, and a protective film bonded to the absorptive polarizing film; cutting the first laminate into a predetermined shape to obtain a sheet-like first laminate; preparing a sheet-like second laminate having a retardation member having first and second principal surfaces opposed to each other, and a first adhesive layer disposed on the first principal surface side of the retardation member; and peeling the protective film from the sheet-like first laminate and bonding the absorptive polarizing film of the sheet-like first laminate to the first adhesive layer of the sheet-like second laminate, wherein the thickness of the absorptive polarizing film is 7 μm or less, and the tensile modulus of elasticity of the protective film is smaller than the tensile modulus of elasticity of the substrate. 2. In the manufacturing method described in 1 above, the tensile modulus of the protective film is 1.0×10 9 It may be less than Pa. 3. In the manufacturing method according to the above 1 or 2, the peeling force of the protective film from the absorptive polarizing film may be less than 0.01 N / 50 mm. 4. In the manufacturing method according to any one of the above items 1 to 3, the protective film may be a self-adhesive film. 5. In the manufacturing method according to any one of 1 to 4 above, the protective film may have a haze of 3% or more. 6. The manufacturing method according to any one of 1 to 5 above may include, after bonding the absorptive polarizing film to the first pressure-sensitive adhesive layer, peeling the substrate from the absorptive polarizing film. 7. In the manufacturing method according to any one of 1 to 6 above, the sheet-like second laminate may have the same shape in a plan view as the first laminate after the cutting. 8. In the manufacturing method according to any one of 1 to 7 above, the second laminate may have a second pressure-sensitive adhesive layer disposed on the second main surface side of the retardation member. 9. In the manufacturing method according to the above item 8, the second pressure-sensitive adhesive layer may have a thickness greater than a thickness of the first pressure-sensitive adhesive layer. Effect of the Invention

[0008] According to the embodiment of the present invention, it is possible to provide high-quality optical laminates with good yield. [Brief description of the drawings]

[0009] [Figure 1A] 1A to 1C are diagrams illustrating an example of a manufacturing process for an optical laminate according to one embodiment of the present invention. [Figure 1B] This is a continuation of Figure 1A. [Figure 1C] This is a continuation of Figure 1B. [Diagram 2] FIG. 1 is a schematic diagram showing a general configuration of an example of a display system for VR goggles. [Diagram 3] FIG. 2 is a schematic cross-sectional view showing an example of details of an optical laminate. [Figure 4] FIG. 2 is a schematic perspective view showing an example of a multilayer structure included in a reflective polarizing film. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, the embodiments of the present invention will be described with reference to the drawings, but the present invention is not limited to these embodiments. In order to clarify the description, the drawings may be schematic in terms of the width, thickness, shape, etc. of each part compared to the embodiment, but they are merely examples and do not limit the interpretation of the present invention. In addition, in the drawings, the same or equivalent elements are given the same reference numerals, and duplicate descriptions may be omitted.

[0011] (Definition of terms and symbols) The definitions of terms and symbols used in this specification are as follows. (1) Refractive index (nx, ny, nz) "nx" is the refractive index in the direction in which the in-plane refractive index is maximum (i.e., the slow axis direction), "ny" is the refractive index in the direction perpendicular to the slow axis in the plane (i.e., the fast axis direction), and "nz" is the refractive index in the thickness direction. (2) In-plane phase difference (Re) "Re(λ)" is the in-plane retardation measured with light of wavelength λ nm at 23° C. For example, "Re(550)" is the in-plane retardation measured with light of wavelength 550 nm at 23° C. Re(λ) is calculated by the formula: Re(λ)=(nx-ny)×d, where d(nm) is the thickness of the layer (film). (3) Retardation in the thickness direction (Rth) "Rth(λ)" is the retardation in the thickness direction measured with light of wavelength λ nm at 23° C. For example, "Rth(550)" is the retardation in the thickness direction measured with light of wavelength 550 nm at 23° C. Rth(λ) is calculated by the formula: Rth(λ)=(nx-nz)×d, where d(nm) is the thickness of the layer (film). (4) Nz coefficient The Nz coefficient is calculated by Nz=Rth / Re. (5)Angle When angles are referred to herein, the angles include both clockwise and counterclockwise angles relative to a reference direction, so for example, "45°" means ±45°.

[0012] A method for producing an optical laminate according to an embodiment of the present invention includes preparing a first laminate having a substrate, an absorptive polarizing film, and a protective film, cutting the first laminate into a predetermined shape to obtain a sheet-like first laminate, preparing a sheet-like second laminate having a retardation member and a first adhesive layer, and peeling the protective film from the sheet-like first laminate and bonding the absorptive polarizing film of the sheet-like first laminate to the first adhesive layer of the sheet-like second laminate.

[0013] 1A to 1C are diagrams showing an example of a manufacturing process for an optical laminate according to one embodiment of the present invention.

[0014] 1A shows a state in which a protective film 54 is attached to an absorptive polarizing film 28 formed on a substrate 53 to form a first laminate 100. The first laminate 100 is typically long and can be wound into a roll. Here, "long" refers to an elongated shape in which the length is sufficiently longer than the width, for example, a elongated shape in which the length is 10 times or more, preferably 20 times or more, the width.

[0015] The absorptive polarizing film 28 is typically composed of a film containing a dichroic material such as iodine or an organic dye. The thickness of the absorptive polarizing film 28 is, for example, 7 μm or less, and may be 6 μm or less, 5 μm or less, or 4 μm or less. On the other hand, the thickness of the absorptive polarizing film 28 is, for example, 1 μm or more. The absorptive polarizing film 28 having such a thickness can typically be formed on a substrate 53, and can be laminated on another member or layer while being integrated with the substrate 53. The substrate 53 can be appropriately selected depending on the absorptive polarizing film 28 formed on its main surface. A method for forming the absorptive polarizing film 28 on the substrate 53 will be described later.

[0016] The tensile modulus of elasticity of the protective film 54 is smaller than the tensile modulus of elasticity of the base material 53. By satisfying this relationship, the protective film 54 can be easily peeled off in a later step. The tensile modulus of elasticity of the protective film is preferably 1.0×10 9 Pa, more preferably less than 8.0×10 8 Pa or less, and more preferably 6.0×10 8 The tensile modulus of the protective film is, for example, 1.0×10 8 Pa or more.

[0017] The thickness of the protective film 54 is, for example, 10 μm to 150 μm, preferably 20 μm to 100 μm, and more preferably 25 μm to 50 μm.

[0018] The haze of the protective film 54 may be 3% or more, or may be 5% or more. The difference between the haze of the protective film 54 and the haze of the substrate 53 may be 2% or more. The haze of the protective film 54 is, for example, 90% or less.

[0019] A film having adhesive properties (hereinafter referred to as a self-adhesive film) is preferably used as the protective film 54. The self-adhesive film can be temporarily attached to the object to be protected (e.g., the absorptive polarizing film 28) by static electricity. The use of such a film has the advantage that no organic residue (e.g., glue stains caused by adhesive) is left on the object to be protected.

[0020] As the self-adhesive film, typically, a polyolefin film is used. Specifically, the self-adhesive film is preferably composed of polyethylene, polypropylene, or a mixture thereof. Here, polyethylene includes ethylene homopolymer and copolymer of ethylene and other olefins. Polypropylene includes propylene homopolymer and copolymer of propylene and other olefins.

[0021] Specific examples of the polyethylene include high density polyethylene (HDPE), low density polyethylene (LDPE), and linear low density polyethylene (L-LDPE).

[0022] Examples of the other olefins include ethylene, propylene, butene, pentene, hexene, heptene, octene, nonene, and decene. Among these, ethylene, propylene, and butene are preferably used. In preparing a copolymer of ethylene or propylene and other olefins, the blending ratio of the other olefins is preferably 40 parts by weight or less, more preferably 30 parts by weight or less, and even more preferably 20 parts by weight or less, based on 100 parts by weight of the total of ethylene or propylene and other olefins.

[0023] In one embodiment, the polyolefin film preferably contains polyethylene. Specifically, the polyolefin film is preferably a polyethylene film or a mixture film of polyethylene and polypropylene. When the polyolefin film contains a mixture of polyethylene and polypropylene, the content of polyethylene is preferably 60 parts by weight or more and 97 parts by weight or less, more preferably 70 parts by weight or more, and even more preferably 80 parts by weight or more, based on 100 parts by weight of the total of polyethylene and polypropylene.

[0024] The self-adhesive film (e.g., polyolefin film) may contain other components such as particles, pigments, colorants, antistatic agents, ultraviolet absorbers, antioxidants, heat stabilizers, and chlorine scavengers. The self-adhesive film (e.g., polyolefin film) may be a single layer having a uniform composition, or may have a laminated structure of two or more layers having different compositions. Specific examples of the laminated structure include a two-layer structure of a first layer and a second layer having different compositions, and a three-layer structure of a first layer, a second layer, and a third layer. The first layer and the third layer may have substantially the same composition or different compositions. The self-adhesive film (e.g., polyolefin film) may be a non-stretched film or a stretched film, but is preferably a non-stretched film.

[0025] The surface roughness Ra of the adhesive surface of the self-adhesive film (eg, polyolefin film) is, for example, from 0.05 μm to 0.3 μm, and preferably 0.2 μm or less.

[0026] FIG. 1B shows how the first laminate 100 is cut into a desired shape (into sheets). The dashed lines in FIG. 1B indicate the cutting lines. The planar shape of the first laminate 100 after cutting is, for example, rectangular or square. The method for cutting the first laminate 100 is not particularly limited, but for example, the first laminate 100 is cut using a punching blade. In this way, by cutting the absorptive polarizing film 28 with the protective film 54 attached thereto, defects such as adhesion of foreign matter to the absorptive polarizing film 28 can be prevented.

[0027] FIG. 1C shows a process of bonding the absorptive polarizing film 28 of the first laminate 100 to the sheet-like second laminate 200. The sheet-like second laminate 200 has substantially the same shape in plan view as the first laminate 100 after cutting. The shape in plan view of the second laminate 200 is, for example, rectangular or square. The second laminate 200 has a retardation member 30 having a first main surface 30a and a second main surface 30b facing each other, and a first adhesive layer 41 arranged on the first main surface 30a side. The retardation member 30 is typically a λ / 4 member. In addition, the second laminate 200 has a second adhesive layer 42 arranged on the second main surface 30b side, and a release liner 52 is bonded to the surface of the second adhesive layer 42. By bonding the first laminate 100 to the second laminate 200, for example, so as to align the planar viewing angles of both, the optical axis (e.g., absorption axis) of the absorptive polarizing film 28 and the optical axis (e.g., slow axis) of the phase difference member 30 can be precisely aligned.

[0028] Before bonding the absorptive polarizing film 28 of the first laminate 100 to the first adhesive layer 41 of the second laminate 200, the protective film 54 is peeled off from the absorptive polarizing film 28. Since the protective film 54 has the above-mentioned predetermined tensile modulus, the protective film 54 can be peeled off from the absorptive polarizing film 28 while maintaining the very thin absorptive polarizing film 28 in close contact with the substrate 53. If the substrate 53 peels off from the absorptive polarizing film 28 when the protective film 54 is peeled off, this may lead to a decrease in yield. Specifically, the peeling off of the substrate 53 may cause defects such as wrinkles, tears, and distortions at the end of the first laminate 100, making it difficult to bond the corners together. As a result, it may be difficult to perform precise axial alignment. In addition, after bonding the absorptive polarizing film 28 to the first adhesive layer 41, when moving to the next process, the substrate 53 may not provide sufficient protection for the absorptive polarizing film 28. The peeling force of the protective film 54 against the absorptive polarizing film 28 is, for example, less than 0.01 N / 50 mm.

[0029] Although not shown, the surface of the first pressure-sensitive adhesive layer 41 may be protected by a release liner until the absorptive polarizing film 28 is bonded to the first pressure-sensitive adhesive layer 41. The thickness of the release liner protecting the surface of the first pressure-sensitive adhesive layer 41 is preferably significantly different from the thickness of the release liner 52 bonded to the surface of the second pressure-sensitive adhesive layer 42. For example, the difference between the thickness of the release liner protecting the surface of the first pressure-sensitive adhesive layer 41 and the thickness of the release liner 52 bonded to the surface of the second pressure-sensitive adhesive layer 42 is preferably 7 μm or more, more preferably 10 μm or more. By making the thicknesses of the release liners disposed on both sides of the retardation member 30 different, it becomes easy to distinguish the front and back of the retardation member 30, which can contribute to improving workability.

[0030] Unlike the illustrated example, when the first adhesive layer 41 is provided in advance on the absorptive polarizing film 28 side rather than on the retardation member 30 side (when the first laminate 100 has the first adhesive layer 41), it may be necessary to separately manage the product of the first laminate 100. Specifically, depending on the materials constituting the first adhesive layer 41 and / or the absorptive polarizing film 28, it may become necessary to manage the expiration date of the first laminate 100.

[0031] Although not shown, after the absorptive polarizing film 28 is bonded to the first pressure-sensitive adhesive layer 41, another member (including a layer) may be laminated thereon. For example, after the base material 53 is peeled off from the absorptive polarizing film 28, another member may be laminated on the absorptive polarizing film 28. The peeling force of the base material 53 with respect to the absorptive polarizing film 28 is, for example, 0.01 N / 50 mm to 0.06 N / 50 mm. The other member laminated on the absorptive polarizing film 28 may also be in the form of a sheet. The other member may have, for example, substantially the same shape as the first laminate 100 in a plan view.

[0032] The thicknesses of the first pressure-sensitive adhesive layer 41 and the second pressure-sensitive adhesive layer 42 may each be set to any appropriate thickness, but are preferably 3 μm to 20 μm, and more preferably 4 μm to 15 μm. For example, the thickness of the second pressure-sensitive adhesive layer 42 may be set to be greater than the thickness of the first pressure-sensitive adhesive layer 41. By providing a thickness difference, for example, in the second laminate 200, it becomes easier to distinguish between the first main surface 30a side and the second main surface 30b side of the retardation member 30. The difference between the thickness of the second pressure-sensitive adhesive layer 42 and the thickness of the first pressure-sensitive adhesive layer 41 is, for example, 5 μm or more.

[0033] The members (e.g., phase difference member and / or polarizing member) that may be included in the first laminate and the second laminate may have an optical axis. By preparing a sheet-like first laminate and a sheet-like second laminate in advance and laminating them, highly accurate axial alignment is possible. The optical laminate that is highly accurately axially aligned may be used in any appropriate image display device. For example, it may be suitably used in VR goggles. In VR goggles, extremely high accuracy is required for the alignment of the optical axes of the members included in the optical laminate.

[0034] FIG. 2 is a schematic diagram showing an outline of an example of a display system of VR goggles, and shows the arrangement and shape of each component of the display system. The display system 10 includes a display element 12, a reflective polarizing member 14, a first lens unit 16, a half mirror 18, a first λ / 4 member 20, a second λ / 4 member 22, and a second lens unit 24. The reflective polarizing member 14 is disposed in front of the display surface 12a of the display element 12, and can reflect light emitted from the display element 12. The first lens unit 16 is disposed on the optical path between the display element 12 and the reflective polarizing member 14, and the half mirror 18 is disposed between the display element 12 and the first lens unit 16. The first λ / 4 member 20 is disposed on the optical path between the display element 12 and the half mirror 18, and the second λ / 4 member 22 is disposed on the optical path between the half mirror 18 and the reflective polarizing member 14.

[0035] The display element 12 is, for example, a liquid crystal display or an organic EL display, and has a display surface 12a for displaying an image. The light emitted from the display surface 12a passes through, for example, a polarizing member that may be included in the display element 12, and is converted into a first linearly polarized light.

[0036] The first λ / 4 member 20 can convert the first linearly polarized light incident on the first λ / 4 member 20 into the first circularly polarized light. The first λ / 4 member 20 may be provided integrally with the display element 12.

[0037] The half mirror 18 transmits the light emitted from the display element 12 and reflects the light reflected by the reflective polarizing member 14 toward the reflective polarizing member 14. The half mirror 18 is provided integrally with the first lens portion 16.

[0038] The second λ / 4 member 22 can transmit the light reflected by the reflective polarizing member 14 and the half mirror 18 through the reflective polarizing member 14. The second λ / 4 member 22 may be provided integrally with the first lens portion 16.

[0039] The first circularly polarized light output from the first λ / 4 member 20 passes through the half mirror 18 and the first lens portion 16, and is converted into the second linearly polarized light by the second λ / 4 member 22. The second linearly polarized light output from the second λ / 4 member 22 is reflected toward the half mirror 18 without passing through the reflective polarizing member 14. At this time, the polarization direction of the second linearly polarized light incident on the reflective polarizing member 14 is the same as the reflection axis of the reflective polarizing member 14. Therefore, the second linearly polarized light incident on the reflective polarizing member 14 is reflected by the reflective polarizing member 14.

[0040] The second linearly polarized light reflected by the reflective polarizing member 14 is converted into the second circularly polarized light by the second λ / 4 member 22, and the second circularly polarized light emitted from the second λ / 4 member 22 passes through the first lens unit 16 and is reflected by the half mirror 18. The second circularly polarized light reflected by the half mirror 18 passes through the first lens unit 16 and is converted into the third linearly polarized light by the second λ / 4 member 22. The third linearly polarized light passes through the reflective polarizing member 14. At this time, the polarization direction of the third linearly polarized light incident on the reflective polarizing member 14 is the same as the transmission axis of the reflective polarizing member 14. Therefore, the third linearly polarized light incident on the reflective polarizing member 14 passes through the reflective polarizing member 14.

[0041] The light transmitted through the reflective polarizing member 14 passes through the second lens portion 24 and enters the eye 26 of the user.

[0042] The absorption axis of the polarizing member included in the display element 12 and the reflection axis of the reflective polarizing member 14 may be disposed approximately parallel to each other or approximately perpendicular to each other. The angle between the absorption axis of the polarizing member included in the display element 12 and the slow axis of the first λ / 4 member 20 is, for example, 40° to 50°, may be 42° to 48°, or may be about 45°. The angle between the absorption axis of the polarizing member included in the display element 12 and the slow axis of the second λ / 4 member 22 is, for example, 40° to 50°, may be 42° to 48°, or may be about 45°.

[0043] The in-plane retardation Re(550) of the first λ / 4 member 20 is, for example, 100 nm to 190 nm, and may be 110 nm to 180 nm, 130 nm to 160 nm, or 135 nm to 155 nm. The first λ / 4 member 20 preferably exhibits an inverse dispersion wavelength characteristic in which the retardation value increases according to the wavelength of the measurement light. The Re(450) / Re(550) of the first λ / 4 member 20 may be, for example, 0.75 or more and less than 1, or 0.8 or more and 0.95 or less.

[0044] The in-plane retardation Re(550) of the second λ / 4 member 22 is, for example, 100 nm to 190 nm, and may be 110 nm to 180 nm, 130 nm to 160 nm, or 135 nm to 155 nm. The second λ / 4 member 22 preferably exhibits an inverse dispersion wavelength characteristic in which the retardation value increases according to the wavelength of the measurement light. The Re(450) / Re(550) of the second λ / 4 member 22 may be, for example, 0.75 or more and less than 1, or 0.8 or more and 0.95 or less.

[0045] The optical laminate may include, for example, a member provided in the display system. Specifically, the optical laminate may include a phase difference member such as a λ / 4 member. The optical laminate may also include a polarizing member such as a reflective polarizing member or an absorptive polarizing film. The optical laminate may further include other members such as a protective member and an adhesive layer for integrating adjacent members. The thickness of the optical laminate may vary depending on, for example, the type and number of members included, and may be, for example, 50 μm to 400 μm.

[0046] 3 is a schematic cross-sectional view showing an example of the details of the optical laminate. The optical laminate 1 includes a reflective polarizing member 14. The optical laminate 1 further includes an absorptive polarizing film 28 that may be disposed between the reflective polarizing member 14 and the second lens portion 24, for example, from the viewpoint of improving visibility. The absorptive polarizing film 28 is laminated in front of the reflective polarizing member 14 via a pressure-sensitive adhesive layer 43. The reflection axis of the reflective polarizing member 14 and the absorption axis of the absorptive polarizing film 28 may be disposed approximately parallel to each other, and the transmission axis of the reflective polarizing member 14 and the transmission axis of the absorptive polarizing film 28 may be disposed approximately parallel to each other.

[0047] The optical laminate 1 further includes a third λ / 4 member 30 that can be disposed between the absorptive polarizing film 28 and the second lens portion 24. The third λ / 4 member 30 is laminated on the absorptive polarizing film 28 via a first adhesive layer 41. The angle between the absorption axis of the absorptive polarizing film 28 and the slow axis of the third λ / 4 member 30 is, for example, 40° to 50°, or may be 42° to 48°, or may be about 45°. By providing such a member, for example, reflection of external light from the second lens portion 24 side can be prevented. The in-plane retardation Re(550) of the third λ / 4 member 30 is, for example, 100 nm to 190 nm, or may be 110 nm to 180 nm, 130 nm to 160 nm, or may be 135 nm to 155 nm. The third λ / 4 member 30 preferably exhibits an inverse dispersion wavelength characteristic in which the retardation value increases according to the wavelength of the measurement light. The Re(450) / Re(550) of the third λ / 4 member is, for example, not less than 0.75 and less than 1, and may be not less than 0.8 and not more than 0.95.

[0048] The optical laminate 1 includes, for example, a second pressure-sensitive adhesive layer 42 for integration with an adherend (for example, the second lens portion 24), and a release liner 52 is attached to the surface of the second pressure-sensitive adhesive layer 42. For example, the second pressure-sensitive adhesive layer 42 can be protected by the release liner 52.

[0049] 3, the optical laminate 1 may further include a protective member 31 that can be disposed behind the reflective polarizing member 14. The protective member 31 is laminated to the reflective polarizing member 14 via a pressure-sensitive adhesive layer 44.

[0050] In the illustrated example, the optical laminate 1 includes a surface protection film 51 peelably attached to the protective member 31. The surface protection film 51 may be peeled off before the optical laminate 1 is used (for example, before being laminated on the second lens portion 24) or during the manufacturing process of the final product (for example, VR goggles), or may be mounted directly on the final product.

[0051] The optical laminate 1 can be manufactured by the above manufacturing method. Specifically, after forming a laminated portion from the absorption-type polarizing film 28 to the release liner 52 according to the above manufacturing process example, the optical laminate 1 can be obtained by laminating the reflective polarizing member 14 and the protective member 31 on this laminated portion. The optical laminate 1 can be cut into a shape corresponding to, for example, the shape of the first lens portion or the second lens portion of the above display system. For example, the optical laminate 1 can be cut into a substantially elliptical shape, a substantially circular shape, or the like. Then, the optical laminate 1 can be integrally provided on the first lens portion or the second lens portion.

[0052] The above λ / 4 member preferably exhibits a refractive index characteristic of nx > ny ≧ nz. Here, "ny = nz" includes not only the case where ny and nz are exactly equal but also the case where they are substantially equal. Therefore, within a range that does not impair the effects of the present invention, ny < nz may occur. The Nz coefficient of the λ / 4 member is preferably 0.9 to 3, more preferably 0.9 to 2.5, still more preferably 0.9 to 1.5, and particularly preferably 0.9 to 1.3.

[0053] The λ / 4 member can be, for example, a stretched film of a resin film or an alignment and solidification layer of a liquid crystal compound.

[0054] Examples of the resin contained in the above resin film include polycarbonate resins, polyester carbonate resins, polyester resins, polyvinyl acetal resins, polyarylate resins, cyclic olefin resins, cellulose resins, polyvinyl alcohol resins, polyamide resins, polyimide resins, polyether resins, polystyrene resins, acrylic resins, and the like. These resins may be used alone or in combination. Examples of the combination method include blending and copolymerization. When the λ / 4 member exhibits reverse dispersion wavelength characteristics, a resin film containing a polycarbonate resin or a polyester carbonate resin (hereinafter, may be simply referred to as a polycarbonate resin) can be preferably used.

[0055] Any suitable polycarbonate-based resin can be used as the polycarbonate-based resin. For example, the polycarbonate-based resin contains a structural unit derived from a fluorene-based dihydroxy compound, a structural unit derived from an isosorbide-based dihydroxy compound, and a structural unit derived from at least one dihydroxy compound selected from the group consisting of alicyclic diol, alicyclic dimethanol, di-, tri- or polyethylene glycol, and alkylene glycol or spiro glycol. Preferably, the polycarbonate-based resin contains a structural unit derived from a fluorene-based dihydroxy compound, a structural unit derived from an isosorbide-based dihydroxy compound, a structural unit derived from an alicyclic dimethanol and / or a structural unit derived from a di-, tri- or polyethylene glycol; more preferably, it contains a structural unit derived from a fluorene-based dihydroxy compound, a structural unit derived from an isosorbide-based dihydroxy compound, and a structural unit derived from a di-, tri- or polyethylene glycol. The polycarbonate-based resin may contain a structural unit derived from another dihydroxy compound as necessary. Details of polycarbonate-based resins that can be suitably used for λ / 4 components and methods for forming λ / 4 components are described, for example, in JP 2014-10291 A, JP 2014-26266 A, JP 2015-212816 A, JP 2015-212817 A, and JP 2015-212818 A, and the descriptions in these publications are incorporated herein by reference.

[0056] The thickness of the λ / 4 member made of a stretched resin film is, for example, 10 μm to 100 μm, preferably 10 μm to 70 μm, and more preferably 20 μm to 60 μm.

[0057] The above-mentioned liquid crystal compound alignment solidified layer is a layer in which the liquid crystal compound is aligned in a predetermined direction within the layer, and the alignment state is fixed. The "alignment solidified layer" is a concept that includes an alignment solidified layer obtained by hardening a liquid crystal monomer as described below. In a λ / 4 member, typically, rod-shaped liquid crystal compounds are aligned in the slow axis direction of the λ / 4 member (homogeneous alignment). Examples of rod-shaped liquid crystal compounds include liquid crystal polymers and liquid crystal monomers. The liquid crystal compound is preferably polymerizable. If the liquid crystal compound is polymerizable, the alignment state of the liquid crystal compound can be fixed by aligning the liquid crystal compound and then polymerizing it.

[0058] The alignment solidified layer of the liquid crystal compound (liquid crystal alignment solidified layer) can be formed by performing an alignment treatment on the surface of a predetermined substrate, applying a coating liquid containing a liquid crystal compound to the surface to align the liquid crystal compound in a direction corresponding to the alignment treatment, and fixing the alignment state. Any appropriate alignment treatment can be adopted as the alignment treatment. Specifically, mechanical alignment treatment, physical alignment treatment, and chemical alignment treatment can be mentioned. Specific examples of mechanical alignment treatment include rubbing treatment and stretching treatment. Specific examples of physical alignment treatment include magnetic field alignment treatment and electric field alignment treatment. Specific examples of chemical alignment treatment include oblique deposition method and photoalignment treatment. As the treatment conditions of various alignment treatments, any appropriate conditions can be adopted depending on the purpose.

[0059] The alignment of the liquid crystal compound is performed by treating the liquid crystal compound at a temperature at which the liquid crystal compound exhibits a liquid crystal phase according to the type of liquid crystal compound. By performing such temperature treatment, the liquid crystal compound takes on a liquid crystal state and is aligned according to the alignment treatment direction of the substrate surface.

[0060] In one embodiment, the alignment state is fixed by cooling the liquid crystal compound aligned as described above. When the liquid crystal compound is polymerizable or crosslinkable, the alignment state is fixed by subjecting the liquid crystal compound aligned as described above to a polymerization treatment or crosslinking treatment.

[0061] As the liquid crystal compound, any suitable liquid crystal polymer and / or liquid crystal monomer is used. The liquid crystal polymer and the liquid crystal monomer may be used alone or in combination. Specific examples of the liquid crystal compound and the method for producing the liquid crystal alignment solidified layer are described in, for example, JP 2006-163343 A, JP 2006-178389 A, and WO 2018 / 123551 A. The descriptions in these publications are incorporated herein by reference.

[0062] The thickness of the second λ / 4 member constituted by the liquid crystal alignment solidified layer is, for example, 1 μm to 10 μm, preferably 1 μm to 8 μm, more preferably 1 μm to 6 μm, and further preferably 1 μm to 4 μm.

[0063] The reflective polarizing element transmits polarized light (typically, linearly polarized light) parallel to its transmission axis while maintaining its polarization state, and can reflect light in other polarization states. The reflective polarizing element is typically composed of a film having a multilayer structure (sometimes referred to as a reflective polarizing film). In this case, the thickness of the reflective polarizing element is, for example, 10 μm to 150 μm, preferably 20 μm to 100 μm, and more preferably 30 μm to 60 μm.

[0064] FIG. 4 is a schematic perspective view showing an example of a multilayer structure included in a reflective polarizing film. The multilayer structure 14a has a layer A having birefringence and a layer B having substantially no birefringence alternately. The total number of layers constituting the multilayer structure may be 50 to 1000. For example, the refractive index nx in the x-axis direction of the A layer is larger than the refractive index ny in the y-axis direction, and the refractive index nx in the x-axis direction and the refractive index ny in the y-axis direction of the B layer are substantially the same, and the refractive index difference between the A layer and the B layer is large in the x-axis direction and substantially zero in the y-axis direction. As a result, the x-axis direction can be the reflection axis, and the y-axis direction can be the transmission axis. The refractive index difference between the A layer and the B layer in the x-axis direction is preferably 0.2 to 0.3.

[0065] The A layer is typically made of a material that develops birefringence through stretching. Examples of such materials include naphthalene dicarboxylic acid polyesters (e.g., polyethylene naphthalate), polycarbonates, and acrylic resins (e.g., polymethyl methacrylate). The B layer is typically made of a material that does not substantially develop birefringence even when stretched. Examples of such materials include copolyesters of naphthalene dicarboxylic acid and terephthalic acid. The multilayer structure can be formed by combining coextrusion and stretching. For example, the material constituting the A layer and the material constituting the B layer are extruded, and then multilayered (e.g., using a multiplier). The resulting multilayer laminate is then stretched. The x-axis direction in the illustrated example can correspond to the stretching direction.

[0066] Commercially available reflective polarizing films include, for example, products manufactured by 3M under the trade names "DBEF" and "APF" and products manufactured by Nitto Denko Corporation under the trade name "APCF."

[0067] The crossed transmittance (Tc) of the reflective polarizing member (reflective polarizing film) may be, for example, 0.001% to 3%. The single transmittance (Ts) of the reflective polarizing member (reflective polarizing film) may be, for example, 43% to 49%, and preferably 45% to 47%. The degree of polarization (P) of the reflective polarizing member (reflective polarizing film) may be, for example, 92% to 99.99%.

[0068] The crossed transmittance, single transmittance and degree of polarization can be measured, for example, using an ultraviolet-visible spectrophotometer. The degree of polarization P can be calculated from the obtained Tp and Tc by measuring the single transmittance Ts, parallel transmittance Tp and crossed transmittance Tc using an ultraviolet-visible spectrophotometer, using the following formula. Note that Ts, Tp and Tc are Y values ​​measured using a 2-degree visual field (C light source) according to JIS Z 8701 and corrected for visibility. Polarization degree P(%)={(Tp-Tc) / (Tp+Tc)} 1 / 2 ×100

[0069] As described above, the absorptive polarizing film is typically composed of a film containing a dichroic material such as iodine or an organic dye. The crossed transmittance (Tc) of the absorptive polarizing film is preferably 0.5% or less, more preferably 0.1% or less, and further preferably 0.05% or less. The single transmittance (Ts) of the absorptive polarizing film is, for example, 41.0% to 45.0%, and preferably 42.0% or more. The polarization degree (P) of the absorptive polarizing film is, for example, 99.0% to 99.997%, and preferably 99.8% or more.

[0070] For example, the absorptive polarizing film may be made of a liquid crystal compound. The thickness of the absorptive polarizing film made of a liquid crystal compound may be, for example, 4 μm or less, may be 3 μm or less, or may be 2 μm or less.

[0071] As the liquid crystal compound, a lyotropic liquid crystal polymer is preferably used. The liquid crystal compound is typically aligned in a predetermined direction in the absorptive polarizing film, and the alignment state is fixed. Specifically, the absorptive polarizing film may be an alignment-solidified layer of the liquid crystal compound. The liquid crystal phase of the liquid crystal compound may be, for example, any of a nematic phase, a smectic phase, and a columnar phase.

[0072] The lyotropic liquid crystal polymer has, for example, a structural unit containing a ring structure, a linking group, and a sulfo group and / or a sulfonate group. The ring structure is typically contained in the main chain of the lyotropic liquid crystal polymer. The number of ring structures contained in each structural unit is, for example, 1 to 5. A typical example of the ring structure is an aromatic ring. Examples of the ring structure include a benzene ring, an oxazole ring, a thiazole ring, an oxadiazole ring, a biphenyl ring, and condensed rings thereof. A benzene ring is preferably used. The linking group links, for example, two ring structures. Both ends of the linking group are, for example, directly bonded to the ring structures. Examples of the linking group include sp 3 Carbon-containing linking groups include amide bonds. 3 A carbon-containing linking group is used. 3Specific examples of the carbon-containing linking group include an alkylene group and an oxyalkylene group. Preferably, an alkylene group having 1 to 8 carbon atoms is used, and more preferably, a methylene group or an ethylene group is used.

[0073] The sulfo group and / or sulfonate group can impart water solubility and lyotropic liquid crystallinity to the lyotropic liquid crystal polymer. The sulfo group and / or sulfonate group is, for example, directly bonded to a ring structure. The number of sulfo groups and / or sulfonate groups contained in each constitutional unit is, for example, 1 to 5. Representative examples of the counter cation of the sulfonate group include alkali metal cations, and preferably Li + , Na + , K + , Rb + , Cs + By exchanging the counter cation of the sulfonate group for a cation with a lower water solubility (so-called insolubilization treatment), an absorptive polarizing film with excellent water resistance can be obtained. Representative examples of cations with a lower water solubility than alkali metal cations include ammonium ions and polyvalent metal cations. Representative examples of the ammonium ions used are ammonium ions of organic nitrogen compounds having two or more nitrogen atoms in the molecule. The number of nitrogen atoms contained in the organic nitrogen compound is not particularly limited, but is preferably 2 to 5, more preferably 2 to 3, and even more preferably 2. Examples of polyvalent metal cations include alkaline earth metal cations (e.g., Ca 2+ , Mg 2+ , Sr 2+ , B.A. 2+ ), transition metal cations (e.g., La 3+ , Fe 3+ , Cr 3+ , Mn 2+ , Cu 2+ , Ce 3+ ), poor metal cations (e.g., Al 3+ , Pb 2+ , Sn 2+ , Zn 2+ ) are mentioned.

[0074] Examples of the structural unit of the lyotropic liquid crystal polymer include structures shown in the following formulae (1) to (23). Here, formulae (1), (3) to (10) show structural units having an alkylene group (linking group) and a benzene ring (ring structure). Formula (2) shows structural units having an amide bond (linking group) and a benzene ring (ring structure). Formulae (11) to (19) show structural units having an alkylene group (linking group) and a condensed ring (ring structure). Formulae (20) to (23) show structural units having an oxyalkylene group (linking group) and a benzene ring (ring structure). Although the following formulae (2) to (23) contain a sulfo group for convenience, they may be sulfonate groups.

[0075] [ka] (In formula (1), X represents a hydrogen atom or a counter cation selected from an ammonium ion, an alkali metal cation, an alkaline earth metal cation, a transition metal cation, or a poor metal cation.)

[0076] [ka]

[0077] [ka]

[0078] [ka]

[0079] [ka]

[0080] Among these structural units, structural units having an alkylene group (linking group) and a benzene ring (ring structure) (the above formulas (1), (3) to (10)), structural units having an amide bond (linking group) and a benzene ring (ring structure) (the above formula (2)) are preferably used, and the structural unit represented by the above formula (1) is more preferably used. The lyotropic liquid crystalline polymer may, for example, have one of the above structural units alone, or may have a combination of a plurality of structural units. The lyotropic liquid crystalline polymer is preferably a homopolymer having one of the above structural units alone, more preferably a homopolymer of the structural unit represented by the above formula (1) or (2), and even more preferably a homopolymer of the structural unit represented by the above formula (1).

[0081] In the lyotropic liquid crystalline polymer, the number of repeating constitutional units is, for example, 25 or more and 1000 or less. The lyotropic liquid crystalline polymer itself may be transparent and does not substantially exhibit absorption dichroism. The single transmittance of the lyotropic liquid crystalline polymer is, for example, 85% or more and 100% or less.

[0082] In one embodiment, the absorptive polarizing film made of a liquid crystal compound may contain an organic dye capable of imparting absorptive dichroism as a dichroic material. Examples of such organic dyes include the organic dyes represented by the following formulas (24) to (26). [ka] In formula (24), A represents a sulfo group or a sulfonate group. m represents 1 or more and 4 or less. B represents a chlorine atom. p represents 0 or more and 2 or less. m+p is 4 or less. When A is a sulfonate group, its counter cation is Na + , K + , Cs + , or NH4 + It is.) [ka] In formula (25), A represents a sulfo group or a sulfonate group. m represents 1 or more and 4 or less. B represents a hydroxyl group. p represents 0 or more and 4 or less. C represents a sulfonyl group. n represents 0 or more and 2 or less. R represents an oxygen atom. q represents 0 or more and 4 or less. m+p+q is 6 or less. When A is a sulfonate group, its counter cation is Na + , K + , Cs + , or NH4 + It is.) [ka] In formula (26), A represents a sulfo group or a sulfonate group. When A represents a sulfonate group, its counter cation is Na + , K + , Cs + , or NH4 + It is.)

[0083] Examples of organic dyes include azo dyes, azoxy dyes, azomethine dyes, stilbene dyes, polymethine dyes, cationic dyes, naphthalene dyes, perylene dyes, and anthrone dyes described in paragraphs

[0035] to

[0037] of JP-A No. 2004-528603; stilbene dyes described in U.S. Pat. No. 5,007,942 or U.S. Pat. No. 5,340,504; and azo and metallized dyes described in European Patent No. 0 530 106, European Patent Application Publication No. 0 626 598, or U.S. Pat. No. 5,318,856.

[0084] In addition, examples of organic dyes include CI Direct Yellow 12, CI Direct Yellow 28, CI Direct Yellow 44, CI Direct Yellow 142, CI Direct Orange 6, CI Direct Orange 26, CI Direct Orange 39, CI Direct Orange 72, CI Direct Orange 107, CI Direct Red 2, CI Direct Red 31, CI Direct Red 79, CI Direct Red 81, CI Direct Red 240, CI Direct Red 247, CI Direct Violet 9, CI Direct Violet 48, CI Direct Violet 51, CI Direct Blue 1, CI Direct Blue 15, CI Direct Blue 71, CI Direct Blue 78, CI Direct Blue 98, CI Direct Blue 168, CI Direct Blue 202, CI Direct Blue 203, CI Direct Blue 204, CI Direct Blue 205, CI Direct Blue 206, CI Direct Blue 207, CI Direct Blue 209, CI Direct Blue 210, CI Direct Blue 211, CI Direct Blue 212, CI Direct Blue 213, CI Direct Blue 214, CI Direct Blue 215, CI Direct Blue 216, CI Direct Blue 217, CI Direct Blue 218, CI Direct Blue 219, CI Direct Blue 220, CI Direct Blue 221, CI Direct Blue 222, CI Direct Blue 223, CI Direct Blue 224, CI Direct Blue 225, CI Direct Blue 226, CI Direct Blue 227, CI Direct Blue 228, CI Direct Blue 229, CI Direct Blue 230, CI Direct Blue 231, CI Direct Blue 232, CI Direct Blue 233, CI Direct Blue 234, CI Direct Blue 235, CI Direct Blue 2 Direct dyes such as CI Direct Brown 106, CI Direct Brown 223, CI Direct Green 85; Active dyes such as CI Active Yellow 1, CI Active Red 1, CI Active Red 6, CI Active Red 14, CI Active Red 46, CI Active Violet 1, CI Active Blue 9, CI Active Blue 10; Acid dyes such as CI Acid Orange 63, CI Acid Red 85, CI Acid Red 144, CI Acid Red 152, CI Acid Brown 32, CI Acid Violet 50, CI Acid Blue 18, CI Acid Blue 44, CI Acid Blue 61, CI Acid Blue 102, CI Acid Black 21; Cationic dyes such as CI Basic Red 12, Basic Brown (CI 33500), CI Basic Black.

[0085] Further, organic dyes include, for example, organic molecules described in U.S. Patent Application Publication No. 2001 / 0029638. Specific examples include polymethine dyes (e.g., pseudoisocyanine, piacyanol), triarylmethane dyes (e.g., Basic Turquose, Acid Light Blue 3), diaminoxanthene dyes (e.g., sulforhodamine), acridine dyes (e.g., Basic Yellow K), sulfonated acridine dyes (e.g., trans-quinacridone), water-soluble derivatives of anthraquinone dyes (e.g., Activite Light Blue KX), sulfonated vat dyes (e.g., Flavanthrone, Indanthrene Yellow, Vat Yellow 4K, Vat Dark Green G, Vat Violet C, Indanthrone, Perylene Violet, Vat Scarlet 2G), azo dyes (e.g., Benzopurpurin 4B, Direct Lightfast Yellow, O), water soluble diazine dyes (e.g., Acid Dark Blue 3), sulfonated dioxazine dyes (e.g., Pigment Violet Dioxazine), soluble thiazine dyes (e.g., Methylene Blue), water soluble phthalocyanine derivatives (e.g., copper octacarboxyphthalocyanine salts), disodium cromoglycanate, perylenetetracarboxylic diimide red (PADR), benzimidazole of PADR (i.e., purple), naphthalenetetracarboxylic acid (i.e., yellow, deep red-purple), phenanthro-9',10':2,3-quinoxaline, and sulfo derivatives of benzimidazoles.

[0086] Such organic dyes may be used alone or in combination of two or more. In a preferred embodiment, the organic dyes represented by the above formulas (24) to (26) are used in combination.

[0087] The absorptive polarizing film made of a liquid crystal compound can be obtained, for example, by coating a liquid crystal polymer solution in which the above-mentioned lyotropic liquid crystal polymer is dissolved in an aqueous solvent on a substrate, drying the liquid crystal polymer solution to form a lyotropic liquid crystal layer, and then dyeing the lyotropic liquid crystal layer. After dyeing, excess dye solution can be removed.

[0088] The thickness of the substrate is, for example, 10 μm to 80 μm. The tensile modulus of the substrate is preferably 1.0×10 9 Pa or more, more preferably 1.2×10 9 Pa or more, and more preferably 1.5×10 9 The tensile modulus of the substrate is, for example, 1.0×10 10 Pa or less. The haze of the substrate is, for example, 2% or less. The substrate may be made of any suitable film. Examples of materials that are the main components of the film that constitutes the substrate include cellulose resins such as triacetyl cellulose (TAC), polyesters such as polyethylene terephthalate (PET), polyvinyl alcohols, polycarbonates, polyamides, polyimides, polyethersulfones, polysulfones, polystyrenes, cycloolefins such as polynorbornene, polyolefins, (meth)acrylics, and acetates. For example, a TAC film or a PET film is preferably used as the substrate. Such a film satisfactorily satisfies the above tensile modulus, and has the advantages of being less likely to deform during the coating and drying, and being less likely to cause defects such as dents and scratches when wound up after coating and drying. On the other hand, when used on a substrate that is less likely to deform, it tends to be difficult to peel the substrate from the absorptive polarizing film after the formation of the absorptive polarizing film. When the thickness of the resulting absorptive polarizing film is very thin, this tendency may be significant.

[0089] Examples of the aqueous solvent include water and a mixed solvent of water and alcohol, and water is preferably used. The solid content concentration in the liquid crystal polymer solution is, for example, 5% by mass or more and 30% by mass or less, and preferably 10% by mass or more and 20% by mass or less. When the liquid crystal polymer solution is applied, a primer layer (containing, for example, polyethyleneimine) may be formed on the coated surface of the substrate. The thickness of the primer layer is, for example, 10 nm or more and 50 nm or less. The liquid crystal polymer solution can be applied by a coating method capable of applying a shear stress. A wire bar is typically used for the coating. The coated film of the liquid crystal polymer solution can be dried to form a lyotropic liquid crystal layer. The drying temperature is, for example, 40° C. or more and 80° C. or less, and preferably 50° C. or more and 70° C. or less. The drying time is, for example, 10 seconds or more and 10 minutes or less, and preferably 5 minutes or less. The lyotropic liquid crystal polymer can be oriented by the shear stress during application, and the lyotropic liquid crystal layer can exhibit a retardation having a slow axis in the application direction.

[0090] The dyeing can be typically performed by immersing the lyotropic liquid crystal layer in a dyeing solution containing a dichroic material. The temperature of the dyeing solution during dyeing is, for example, from 10° C. to 50° C., and preferably from 20° C. to 40° C. The immersion time (dyeing time) is, for example, from 5 seconds to 300 seconds, and preferably from 30 seconds to 180 seconds.

[0091] When the dichroic substance is iodine, the dyeing solution preferably further contains an iodine compound, more preferably an iodine compound and a polyvalent metal salt. Examples of the iodine compound include potassium iodide, lithium iodide, sodium iodide, zinc iodide, aluminum iodide, lead iodide, copper iodide, barium iodide, calcium iodide, tin iodide, and titanium iodide. Potassium iodide is preferably used. The mass ratio of iodine to the iodine compound in the dyeing solution (iodine:iodine compound) is, for example, 1:5 to 1:30, and preferably 1:5 to 1:15. The dyeing solution contains a polyvalent metal salt, which can impart water resistance to the absorptive polarizing film. Examples of the polyvalent metal salt include chlorides, sulfates, nitrates, phosphates, oxalates, and acetates. The counter metal of the polyvalent metal salt may be, for example, an alkali metal, an alkaline earth metal, a transition metal, or a non-metallic metal, specifically, barium, aluminum, lead, chromium, strontium, cerium, lanthanum, samarium, yttrium, copper, or iron. Strontium chloride is preferably used. The mass ratio of iodine to the polyvalent metal salt in the dyeing solution (iodine:polyvalent metal salt) is, for example, 1:5 to 1:30, and preferably 1:5 to 1:15.

[0092] When the dichroic material is an organic dye, the solids concentration of the organic dye in the dye solution is, for example, 0.1% by mass to 3.0% by mass, and preferably 1.0% by mass or more. When the organic dyes represented by the above formulas (24) to (26) are used in combination, the mass ratio of formulas (24):(25):(26) is, for example, 40-60:10-30:10-30.

[0093] For example, the absorptive polarizing film may be made of a resin film, and in this case, the absorptive polarizing film is preferably a polyvinyl alcohol (PVA) film containing iodine.

[0094] An example of a method for producing an absorptive polarizing film made of a resin film includes forming a polyvinyl alcohol-based resin layer (PVA-based resin layer) containing a polyvinyl alcohol-based resin (PVA-based resin) and a halide on one side of a long thermoplastic resin substrate to form a laminate, and subjecting the laminate to an auxiliary air-stretching treatment, a dyeing treatment, an underwater stretching treatment, and a drying shrinkage treatment in this order, in which the laminate is heated while being transported in the longitudinal direction to shrink the laminate by 2% or more in the width direction. The thickness of the obtained absorptive polarizing film can be controlled, for example, by adjusting the stretching ratio in the underwater stretching treatment.

[0095] The PVA-based resin layer is preferably formed by applying a coating liquid containing a PVA-based resin and a halide to a thermoplastic resin substrate and drying the coating liquid. The content of the halide in the PVA-based resin layer is preferably 5 to 20 parts by weight per 100 parts by weight of the PVA-based resin. The thickness of the PVA-based resin layer is preferably 3 to 40 μm, and more preferably 3 to 20 μm.

[0096] Examples of the method for applying the coating liquid include roll coating, spin coating, wire bar coating, dip coating, die coating, curtain coating, spray coating, knife coating (comma coating, etc.), etc. The application and drying temperature of the coating liquid is preferably 50° C. or higher.

[0097] From the viewpoint of improving the adhesion between the thermoplastic resin substrate and the PVA-based resin layer, the thermoplastic resin substrate may be subjected to a surface treatment such as a corona treatment before the PVA-based resin layer is formed, or an easy-adhesion layer may be formed on the thermoplastic resin substrate.

[0098] The thickness of the thermoplastic resin substrate is preferably 20 μm to 300 μm, more preferably 50 μm to 200 μm. If it is less than 20 μm, for example, it may be difficult to form a PVA-based resin layer. If it exceeds 300 μm, for example, in the underwater stretching treatment described below, it may take a long time for the thermoplastic resin substrate to absorb water, and an excessive load may be required for stretching.

[0099] The water absorption of the thermoplastic resin substrate is preferably 0.2% or more, more preferably 0.3% or more. The thermoplastic resin substrate can absorb water, and the water can act as a plasticizer to plasticize the substrate. As a result, the stretching stress can be significantly reduced, and the substrate can be stretched at a high ratio. On the other hand, the water absorption of the thermoplastic resin substrate is preferably 3.0% or less, more preferably 1.0% or less. By using such a thermoplastic resin substrate, it is possible to prevent problems such as a significant decrease in the dimensional stability of the substrate during production, which leads to a deterioration in the appearance of the obtained absorptive polarizing film. It is also possible to prevent the substrate from breaking during underwater stretching, and the PVA-based resin layer from peeling off from the substrate. The water absorption of the thermoplastic resin substrate can be adjusted, for example, by introducing a modifying group into the constituent material. The water absorption is a value determined in accordance with JIS K 7209.

[0100] The glass transition temperature (Tg) of the thermoplastic resin substrate is preferably 120° C. or less. By using such a thermoplastic resin substrate, the stretchability of the laminate can be sufficiently ensured while suppressing the crystallization of the PVA-based resin layer. In consideration of the plasticization of the thermoplastic resin substrate by water and the good underwater stretching, the Tg is more preferably 100° C. or less, and further preferably 90° C. or less. On the other hand, the Tg of the thermoplastic resin substrate is preferably 60° C. or more. By using such a thermoplastic resin substrate, defects such as deformation of the substrate (e.g., generation of unevenness, sagging, wrinkles, etc.) during the coating and drying of the coating liquid can be prevented, and a laminate can be produced well. In addition, the stretching of the PVA-based resin layer can be performed at a suitable temperature (e.g., about 60° C.). The glass transition temperature of the thermoplastic resin substrate can be adjusted, for example, by introducing a modifying group into the constituent material or by heating using a crystallizing material. The glass transition temperature (Tg) is a value obtained in accordance with JIS K 7121.

[0101] Examples of the thermoplastic resin include ester resins such as polyethylene terephthalate resins, cycloolefin resins such as norbornene resins, olefin resins such as polypropylene, polyamide resins, polycarbonate resins, and copolymer resins thereof. Among these, norbornene resins and amorphous polyethylene terephthalate resins are preferably used.

[0102] In one embodiment, amorphous (uncrystallized) polyethylene terephthalate resins are preferably used. Among them, amorphous (hard to crystallize) polyethylene terephthalate resins are preferably used. Specific examples of amorphous polyethylene terephthalate resins include copolymers further containing isophthalic acid and / or cyclohexanedicarboxylic acid as dicarboxylic acids, and copolymers further containing cyclohexanedimethanol or diethylene glycol as glycols.

[0103] In a preferred embodiment, the thermoplastic resin substrate is made of a polyethylene terephthalate resin having an isophthalic acid unit. Such a thermoplastic resin substrate has excellent stretchability and can suppress crystallization during stretching. This is believed to be due to the introduction of an isophthalic acid unit, which gives a large bend to the main chain. The polyethylene terephthalate resin has a terephthalic acid unit and an ethylene glycol unit. The content ratio of the isophthalic acid unit is preferably 0.1 mol% or more, more preferably 1.0 mol% or more, based on the total of all repeating units. This is because a thermoplastic resin substrate with extremely excellent stretchability can be obtained. On the other hand, the content ratio of the isophthalic acid unit is preferably 20 mol% or less, more preferably 10 mol% or less, based on the total of all repeating units. By setting such a content ratio, the crystallinity can be favorably increased in the drying shrinkage treatment described below.

[0104] The thermoplastic resin substrate may be stretched by any appropriate method before forming the PVA-based resin layer. For example, the long thermoplastic resin substrate may be stretched in the transverse direction. The transverse direction is preferably a direction substantially perpendicular to the stretching direction of the laminate described below. The stretching temperature of the thermoplastic resin substrate is preferably Tg-10°C to Tg+50°C relative to the glass transition temperature (Tg). The stretching ratio of the thermoplastic resin substrate is preferably 1.5 to 3.0 times.

[0105] As described above, the coating liquid may contain a PVA resin and a halide. The coating liquid may typically be a solution in which a PVA resin and a halide are dissolved in a solvent. Examples of the solvent include water, dimethylsulfoxide, dimethylformamide, dimethylacetamide, N-methylpyrrolidone, various glycols, polyhydric alcohols such as trimethylolpropane, and amines such as ethylenediamine and diethylenetriamine. Among these, water is preferably used. The concentration of the PVA resin is preferably 3 to 20 parts by weight relative to 100 parts by weight of the solvent. The content of the halide in the coating liquid is preferably 5 to 20 parts by weight relative to 100 parts by weight of the PVA resin, and more preferably 10 to 15 parts by weight.

[0106] Examples of the PVA resin include polyvinyl alcohol and ethylene-vinyl alcohol copolymer. Polyvinyl alcohol is obtained by saponifying polyvinyl acetate. Ethylene-vinyl alcohol copolymer is obtained by saponifying ethylene-vinyl acetate copolymer. The saponification degree of the PVA resin is, for example, 85 mol% to 100 mol%, preferably 95.0 mol% to 99.95 mol%, and more preferably 99.0 mol% to 99.93 mol%. The saponification degree can be determined in accordance with JIS K 6726-1994. The average polymerization degree of the PVA resin is, for example, 1000 to 10000, preferably 1200 to 4500, and more preferably 1500 to 4300. The average polymerization degree can be determined in accordance with JIS K 6726-1994. Examples of the halide include iodides such as potassium iodide, sodium iodide, and lithium iodide, and sodium chloride. Of these, potassium iodide is preferably used.

[0107] The coating liquid may contain additives. Examples of additives include plasticizers and surfactants. Examples of plasticizers include polyhydric alcohols such as ethylene glycol and glycerin. Examples of surfactants include nonionic surfactants.

[0108] The orientation of the polyvinyl alcohol molecules in the PVA-based resin can be increased by stretching the PVA-based resin layer, but when the stretched PVA-based resin layer is immersed in a liquid containing water, the orientation of the polyvinyl alcohol molecules may be disturbed and the orientation may be reduced. When a laminate of a thermoplastic resin and a PVA-based resin layer is stretched in boric acid water at a relatively high temperature in order to stabilize the stretching of the thermoplastic resin, the orientation tends to be significantly reduced. In contrast, by performing high-temperature stretching (auxiliary stretching) in air before stretching a laminate of a PVA-based resin layer containing a halide and a thermoplastic resin substrate in boric acid water, crystallization of the PVA-based resin in the PVA-based resin layer of the laminate after the auxiliary stretching can be promoted. As a result, when the PVA-based resin layer is immersed in a liquid, the orientation of the polyvinyl alcohol molecules is disturbed and the orientation is reduced, compared to when the PVA-based resin layer does not contain a halide. This can improve the optical properties of an absorptive polarizing film obtained through a process in which the laminate is immersed in a liquid, such as a dyeing process and an underwater stretching process.

[0109] In order to obtain high optical properties, a two-stage stretching method may be selected, combining air-stretching (auxiliary stretching) and stretching in boric acid water. By introducing auxiliary stretching, the thermoplastic resin substrate can be stretched while suppressing crystallization, which solves the problem of the thermoplastic resin substrate being excessively crystallized and reduced in stretchability in the subsequent boric acid water stretching, and the laminate can be stretched at a high magnification. In addition, when applying a PVA-based resin onto a thermoplastic resin substrate, it is necessary to lower the application temperature, for example, compared to when applying a PVA-based resin onto a metal drum, in order to suppress the influence of the glass transition temperature of the thermoplastic resin substrate. As a result, the crystallization of the PVA-based resin becomes relatively low, and a problem of insufficient optical properties can be obtained. In contrast, by introducing auxiliary stretching, even when applying a PVA-based resin onto a thermoplastic resin, it is possible to increase the crystallinity of the PVA-based resin, and to achieve high optical properties. At the same time, by increasing the orientation of the PVA-based resin in advance, problems such as a decrease in the orientation of the PVA-based resin or dissolution when the resin is immersed in water during subsequent dyeing or stretching processes can be prevented, and high optical properties can be achieved.

[0110] The method of the auxiliary in-air stretching may be fixed-end stretching (e.g., a method of stretching using a tenter stretching machine) or free-end stretching (e.g., a method of uniaxially stretching a laminate by passing it between rolls having different peripheral speeds). From the viewpoint of obtaining high optical properties, free-end stretching is preferably used.

[0111] The stretching ratio of the auxiliary air-stretching is preferably 2.0 to 3.5 times. The auxiliary air-stretching may be performed in one stage or multiple stages. When performed in multiple stages, the stretching ratio is the product of the stretching ratios in each stage. The stretching direction in the auxiliary air-stretching is preferably approximately the same as the stretching direction in the underwater stretching.

[0112] The stretching temperature of the auxiliary air stretching is preferably equal to or higher than the glass transition temperature (Tg) of the thermoplastic resin substrate, more preferably equal to or higher than Tg+10°C of the thermoplastic resin substrate, and even more preferably equal to or higher than Tg+15°C of the thermoplastic resin substrate. On the other hand, the upper limit of the stretching temperature is preferably 170°C. By stretching at such a temperature, the crystallization of the PVA-based resin can be prevented from progressing rapidly, and defects due to crystallization (for example, preventing the orientation of the PVA-based resin layer due to stretching) can be prevented. The crystallization index of the PVA-based resin after the auxiliary air stretching is preferably 1.3 to 1.8, more preferably 1.4 to 1.7. The crystallization index of the PVA-based resin can be measured by the ATR method using a Fourier transform infrared spectrophotometer. Specifically, the measurement is performed using polarized light as the measurement light, and the crystallization index at 1141 cm of the obtained spectrum is measured. -1 and 1440cm -1 The crystallization index is calculated according to the following formula using the intensity of Crystallization index=(I C / I R ) Here, I C is 1141cm when the measurement light is incident -1 is the intensity of I R is the 1440 cm -1 is the strength.

[0113] After the auxiliary air-stretching treatment, an insolubilization treatment may be carried out before the underwater stretching treatment or the dyeing treatment. The insolubilization treatment is typically carried out by immersing the PVA-based resin layer in an aqueous solution of boric acid. The insolubilization treatment imparts water resistance to the PVA-based resin layer, and can prevent a decrease in the orientation of PVA when immersed in water. The concentration of the aqueous solution of boric acid used in the insolubilization treatment is preferably 1 to 4 parts by weight per 100 parts by weight of water. The liquid temperature of the insolubilization bath (aqueous solution of boric acid) is preferably 20°C to 50°C.

[0114] The dyeing treatment is typically performed by dyeing the PVA-based resin layer with iodine. Specifically, the dyeing treatment is performed by allowing the PVA-based resin layer to adsorb iodine. As a method for adsorbing iodine, a method of immersing the PVA-based resin layer (laminate) in a dyeing solution (dyeing bath) containing iodine is preferably adopted.

[0115] The dyeing solution is preferably an aqueous iodine solution. In this case, the amount of iodine is preferably 0.05 to 0.5 parts by weight relative to 100 parts by weight of water. In order to increase the solubility of iodine in water, it is preferable to add an iodide to the aqueous iodine solution. Examples of iodides include potassium iodide, lithium iodide, sodium iodide, zinc iodide, aluminum iodide, lead iodide, copper iodide, barium iodide, calcium iodide, tin iodide, and titanium iodide. Among these, potassium iodide is preferably used. The amount of iodide is preferably 0.1 to 10 parts by weight, more preferably 0.3 to 5 parts by weight, relative to 100 parts by weight of water. The temperature of the dyeing solution during dyeing is preferably 20°C to 50°C in order to suppress dissolution of the PVA resin. When the PVA-based resin layer is immersed in the dye solution, the immersion time is preferably 5 seconds to 5 minutes, and more preferably 30 seconds to 90 seconds, in order to ensure the transmittance of the PVA-based resin layer.

[0116] The dyeing conditions (concentration, liquid temperature, immersion time) can be set so that the single transmittance and polarization degree of the resulting absorptive polarizing film are within the above-mentioned ranges. For example, the ratio of the contents of iodine and potassium iodide in the iodine aqueous solution as the dyeing solution is preferably 1:5 to 1:20, more preferably 1:5 to 1:10.

[0117] When a dyeing process is performed continuously after a process (for example, an insolubilization process) in which a laminate is immersed in a treatment bath containing boric acid, the boric acid concentration of the dyeing bath may change over time due to the boric acid contained in the treatment bath being mixed into the dyeing bath, resulting in unstable dyeability. In order to suppress such instability of dyeability, the upper limit of the boric acid concentration of the dyeing bath is adjusted to be preferably 4 parts by weight, more preferably 2 parts by weight, relative to 100 parts by weight of water. On the other hand, the lower limit of the boric acid concentration of the dyeing bath is preferably 0.1 parts by weight, more preferably 0.2 parts by weight, and even more preferably 0.5 parts by weight, relative to 100 parts by weight of water. In one embodiment, a dyeing bath in which boric acid has been blended in advance is used. This can reduce the rate of change in boric acid concentration when the boric acid of the treatment bath is mixed into the dyeing bath. The amount of boric acid preliminarily mixed into the dye bath (i.e., the content of boric acid not derived from the treatment bath) is preferably 0.1 to 2 parts by weight, and more preferably 0.5 to 1.5 parts by weight, per 100 parts by weight of water.

[0118] After the dyeing process, a crosslinking process may be performed before the underwater stretching process. The crosslinking process is typically performed by immersing the PVA-based resin layer in an aqueous boric acid solution. The crosslinking process imparts water resistance to the PVA-based resin layer, and prevents the orientation of the PVA from decreasing when the layer is immersed in high-temperature water in the subsequent underwater stretching process. The concentration of the aqueous boric acid solution used in the crosslinking process is preferably 1 to 5 parts by weight per 100 parts by weight of water. In addition, when the crosslinking process is performed after the dyeing process, it is preferable to further add an iodide. By adding an iodide, it is possible to suppress the elution of iodine adsorbed to the PVA-based resin layer. The amount of the iodide to be added is preferably 1 to 5 parts by weight per 100 parts by weight of water. Specific examples of the iodide are as described above. The liquid temperature of the crosslinking bath (aqueous boric acid solution) is preferably 20°C to 50°C.

[0119] The underwater stretching treatment is performed by immersing the laminate in a stretching bath. The underwater stretching treatment allows stretching at a temperature lower than the glass transition temperature (typically about 80° C.) of the thermoplastic resin substrate or the PVA-based resin layer, and allows the PVA-based resin layer to be stretched while suppressing crystallization. As a result, a polarizing film having excellent optical properties can be produced.

[0120] The stretching method of the laminate can be any appropriate method. Specifically, it may be fixed end stretching or free end stretching (for example, a method of uniaxially stretching the laminate by passing it between rolls having different peripheral speeds). Preferably, free end stretching is selected. The stretching of the laminate may be performed in one stage or multiple stages. When performing the stretching in multiple stages, the stretching ratio of the laminate described below is the product of the stretching ratios in each stage.

[0121] The underwater stretching is preferably performed by immersing the laminate in an aqueous solution of boric acid (stretching in boric acid water). By using an aqueous solution of boric acid as the stretching bath, it is possible to impart to the PVA-based resin layer rigidity that can withstand the tension applied during stretching and water resistance that does not dissolve in water. Specifically, boric acid can generate tetrahydroxyborate anions in the aqueous solution and crosslink with the PVA-based resin through hydrogen bonds. As a result, it is possible to impart rigidity and water resistance to the PVA-based resin layer and stretch it well, and it is possible to produce an absorptive polarizing film with excellent optical properties.

[0122] The boric acid aqueous solution is preferably obtained by dissolving boric acid and / or a borate in water as a solvent. The boric acid concentration is preferably 1 to 10 parts by weight, more preferably 2.5 to 7 parts by weight, and even more preferably 3 to 6 parts by weight, relative to 100 parts by weight of water. By setting the boric acid concentration to 1 part by weight or more, dissolution of the PVA-based resin layer can be effectively suppressed, and an absorptive polarizing film with higher characteristics can be produced. In addition to boric acid or a borate, an aqueous solution obtained by dissolving a boron compound such as borax, glyoxal, glutaraldehyde, or the like in a solvent can also be used.

[0123] Preferably, an iodide is added to the stretching bath (boric acid aqueous solution). By adding an iodide, it is possible to suppress the elution of iodine adsorbed in the PVA resin layer. Specific examples of the iodide are as described above. The concentration of the iodide is preferably 0.05 to 15 parts by weight, more preferably 0.5 to 8 parts by weight, relative to 100 parts by weight of water.

[0124] The stretching temperature (liquid temperature of the stretching bath) is preferably 40°C or higher, more preferably 60°C or higher. At such a temperature, the film can be stretched well. Specifically, as described above, the glass transition temperature (Tg) of the thermoplastic resin substrate is preferably 60°C or higher in relation to the formation of the PVA-based resin layer. In this case, if the stretching temperature is lower than 40°C, the film may not be stretched well even if the plasticization of the thermoplastic resin substrate by water is taken into consideration. On the other hand, the stretching temperature (liquid temperature of the stretching bath) is preferably 85°C or lower, more preferably 75°C or lower. The higher the temperature of the stretching bath, the higher the solubility of the PVA-based resin layer, and the higher the possibility of not obtaining excellent optical properties. The immersion time of the laminate in the stretching bath is preferably 15 seconds to 5 minutes.

[0125] In one embodiment, the stretching ratio in underwater stretching is preferably 1.0 to 2.2 times, more preferably 1.1 to 2.0 times, even more preferably 1.1 to 1.8 times, and particularly preferably 1.2 to 1.6 times. By setting the stretching ratio in underwater stretching in such a range, an absorptive polarizing film that can achieve the durability described below can be obtained without combining a protective layer. In addition, a polarizing film in which breakage along the absorption axis direction is suppressed can be obtained. The total stretching ratio of the laminate is preferably 3.0 to 4.5 times, more preferably 3.0 to 4.3 times, and even more preferably 3.0 to 4.0 times the original length of the laminate.

[0126] In one embodiment, the stretching ratio in underwater stretching is preferably 1.5 times or more, more preferably 3.0 times or more. The total stretching ratio of the laminate is preferably 5.0 times or more, more preferably 5.5 times or more, based on the original length of the laminate. By achieving such a high stretching ratio, an absorptive polarizing film with excellent optical properties can be produced. Such a high stretching ratio can be achieved by employing an underwater stretching method (stretching in boric acid water).

[0127] The drying shrinkage treatment may be performed by zone heating in which the entire zone is heated, or by heating the transport roll (using a so-called heating roll). Preferably, both are used. By drying using a heating roll, it is possible to efficiently suppress the heat curl of the laminate and produce an absorptive polarizing film with excellent appearance. Specifically, by drying the laminate in a state where it is aligned with the heating roll, it is possible to efficiently promote the crystallization of the thermoplastic resin substrate and increase the crystallinity, and even at a relatively low drying temperature, it is possible to satisfactorily increase the crystallinity of the thermoplastic resin substrate. As a result, the rigidity of the thermoplastic resin substrate increases and it becomes in a state where it can withstand the shrinkage of the PVA-based resin layer due to drying, and curling is suppressed. In addition, by using a heating roll, it is possible to dry the laminate while maintaining it in a flat state, so that it is possible to suppress not only curling but also wrinkles. At this time, the optical properties of the laminate can be improved by shrinking it in the width direction by the drying shrinkage treatment. This is because it is possible to effectively increase the orientation of the PVA and the PVA / iodine complex. The shrinkage rate of the laminate in the width direction due to the drying shrinkage treatment is preferably 1% to 10%, more preferably 2% to 8%, and particularly preferably 4% to 6%. By using a heating roll, the laminate can be continuously shrunk in the width direction while being transported, thereby achieving high productivity.

[0128] For example, the drying conditions can be controlled by adjusting the heating temperature of the transport rolls (temperature of the heating rolls), the number of heating rolls, the contact time with the heating rolls, etc. The temperature of the heating rolls is preferably 60°C to 120°C, more preferably 65°C to 100°C, and even more preferably 70°C to 80°C. The crystallinity of the thermoplastic resin can be favorably increased, curling can be favorably suppressed, and excellent strength can be imparted to the laminate. The temperature of the heating rolls can be measured by a contact thermometer. Usually, 2 to 40 transport rolls, preferably 4 to 30 transport rolls are used. The contact time (total contact time) between the laminate and the heating rolls is preferably 1 second to 300 seconds, more preferably 1 to 20 seconds, and even more preferably 1 to 10 seconds.

[0129] The heating roll may be provided in a heating furnace (for example, an oven) or in a normal production line (under room temperature environment). It is preferably provided in a heating furnace equipped with a blowing means. By using drying with a heating roll in combination with hot air drying, it is possible to suppress abrupt temperature changes between the heating rolls, and it is possible to easily control shrinkage in the width direction. The hot air drying temperature is preferably 30°C to 100°C. The hot air drying time is preferably 1 second to 300 seconds. The hot air speed is preferably about 10 m / s to 30 m / s. The wind speed is the wind speed in the heating furnace, and can be measured by a mini-vane type digital anemometer.

[0130] Preferably, after the underwater stretching treatment and before the drying shrinkage treatment, a washing treatment is performed by, for example, immersing the PVA-based resin layer in an aqueous potassium iodide solution.

[0131] By subjecting the PVA-based resin layer to various treatments, an absorptive polarizing film can be obtained. The PVA-based resin layer of the thermoplastic resin substrate can also be subjected to various treatments. The tensile modulus of the thermoplastic resin substrate after the various treatments is, for example, 1.0×10 9 Pa or more 1.0×10 10 The haze of the thermoplastic resin substrate after various treatments is, for example, 2% or less.

[0132] The protective member typically includes a substrate. The substrate may be made of any suitable film. Examples of materials that are the main components of the film that constitutes the substrate include cellulose-based resins such as triacetyl cellulose (TAC), polyester-based, polyvinyl alcohol-based, polycarbonate-based, polyamide-based, polyimide-based, polyethersulfone-based, polysulfone-based, polystyrene-based, cycloolefin-based such as polynorbornene, polyolefin-based, (meth)acrylic, acetate-based, and other resins. Here, (meth)acrylic refers to acrylic and / or methacrylic. The thickness of the substrate is preferably 5 μm to 80 μm, more preferably 10 μm to 50 μm, and even more preferably 15 μm to 40 μm.

[0133] The protective member is preferably composed of a laminated film having a substrate and a surface treatment layer formed on the substrate. The thickness of the laminated film is preferably 10 μm to 80 μm, more preferably 15 μm to 60 μm, and even more preferably 20 μm to 45 μm. The thickness of the surface treatment layer is preferably 0.5 μm to 10 μm, more preferably 1 μm to 7 μm, and even more preferably 2 μm to 5 μm.

[0134] The surface treatment layer typically includes a hard coat layer. The hard coat layer is typically formed by applying a hard coat layer-forming material to a substrate and curing the applied layer. The hard coat layer-forming material typically includes a curable compound as a layer-forming component. The curing mechanism of the curable compound may be, for example, a thermosetting type or a photocurable type. The curable compound may be, for example, a monomer, an oligomer, or a prepolymer. Preferably, a polyfunctional monomer or oligomer is used as the curable compound. The polyfunctional monomer or oligomer may be, for example, a monomer or oligomer having two or more (meth)acryloyl groups, a urethane (meth)acrylate or an oligomer of a urethane (meth)acrylate, an epoxy-based monomer or oligomer, or a silicone-based monomer or oligomer.

[0135] The thickness of the hard coat layer is preferably 0.5 μm to 10 μm, more preferably 1 μm to 7 μm, and further preferably 2 μm to 5 μm.

[0136] The surface treatment layer preferably includes a functional layer. The functional layer preferably functions as an antireflection layer. In a preferred embodiment, the surface treatment layer includes the hard coat layer and the antireflection layer in this order from the substrate side. The thickness of the functional layer is preferably 0.05 μm to 10 μm, more preferably 0.1 μm to 5 μm, and even more preferably 0.1 μm to 2 μm.

[0137] As the surface protection film, typically, a laminate of a base film and a pressure-sensitive adhesive layer is used. Materials for forming the base film include polyester-based polymers such as polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polybutylene terephthalate (PBT), etc.; cellulose-based polymers such as diacetyl cellulose and triacetyl cellulose; polycarbonate-based polymers; (meth)acrylic polymers such as polymethyl methacrylate; and cycloolefin-based polymers such as polynorbornene. These may be used alone or in combination of two or more. The thickness of the base film is preferably 15 μm to 70 μm, more preferably 20 μm to 60 μm, and even more preferably 25 μm to 50 μm. The thickness of the pressure-sensitive adhesive layer is, for example, 5 μm to 15 μm. The self-adhesive film may also be used as the surface protection film.

[0138] The release liner may typically be made of any suitable plastic film. Specific examples of plastic films include polyethylene terephthalate (PET) film, polyethylene film, and polypropylene film. As the release liner, a plastic film whose surface is coated with a release agent is preferably used. Examples of the release agent include silicone-based release agents, fluorine-based release agents, and long-chain alkyl acrylate-based release agents.

[0139] The thickness of the release liner is preferably 30 μm or more, more preferably 40 μm or more, and further preferably 50 μm or more. The thickness of the release liner is, for example, 100 μm or less.

[0140] As shown in the figure, each member included in the optical laminate 1 can be integrated via an adhesive layer (e.g., a pressure-sensitive adhesive layer). The optical laminate 1 may be provided integrally with the second lens portion of the display system by an adhesive layer (e.g., a pressure-sensitive adhesive layer). The adhesive layer may be formed of an adhesive or a pressure-sensitive adhesive. The thickness of the adhesive layer is, for example, 0.05 μm to 30 μm, preferably 0.5 μm to 20 μm, and more preferably 3 μm to 15 μm.

[0141] The adhesive layer may be made of any suitable adhesive. Specific examples include acrylic adhesives, rubber adhesives, silicone adhesives, polyester adhesives, urethane adhesives, epoxy adhesives, and polyether adhesives. By adjusting the type, number, combination, and compounding ratio of the monomers forming the base resin of the adhesive, as well as the compounding amount of the crosslinking agent, reaction temperature, reaction time, etc., an adhesive having desired properties according to the purpose can be prepared. The base resin of the adhesive may be used alone or in combination of two or more. An acrylic resin is preferably used as the base resin. Specifically, the adhesive layer is preferably made of an acrylic adhesive.

[0142] For example, the pressure-sensitive adhesive layer can be formed by coating and drying a pressure-sensitive adhesive composition containing a base resin, additives such as a crosslinking agent, and a solvent. The pressure-sensitive adhesive composition may be directly coated onto the adherend, or may be coated onto a substrate such as a separately prepared base film (e.g., a release liner). Drying is typically performed by heating. From the viewpoint of forming a good pressure-sensitive adhesive layer, the tensile modulus of the base film onto which the pressure-sensitive adhesive composition is coated is preferably 1.0×10 9 Pa or more. EXAMPLES

[0143] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these examples. The thickness, retardation value, haze, tensile modulus, surface roughness Ra, and peel force are values ​​measured by the following measurement methods. Furthermore, unless otherwise specified, "parts" and "%" are based on weight. <Thickness> The thickness of 10 μm or less was measured using a scanning electron microscope (manufactured by JEOL, product name "JSM-7100F"), and the thickness of more than 10 μm was measured using a digital micrometer (manufactured by Anritsu, product name "KC-351C"). <Phase difference value> The phase difference value at each wavelength at 23°C was measured using a Mueller matrix polarimeter (Axometrics, product name "Axoscan"). <Haze> The haze was measured according to JIS 7136 using a haze meter (manufactured by Murakami Color Science Laboratory, product name "HN-150"). <Tensile modulus> The measurement object was molded into a tensile test dumbbell with a parallel part width of 10 mm and a length of 40 mm based on JIS K 6734:2000, which was pulled in the length direction at a tensile speed of 300 mm / min using a tensile tester (Shimadzu Corporation, "Autograph AG-Xplus"), and the tensile modulus was calculated from the slope of the straight line in the obtained stress-strain curve for test forces of 10 N to 20 N. The measurement was performed in an environment of 23°C and a relative humidity of 50% RH. <Surface roughness Ra> The surface roughness Ra was measured using a scanning white light interferometer (Zygo, product name "NewView9000"). Specifically, the measurement sample was placed on a measurement table with a vibration-proof table, interference fringes were generated using a single white LED light, and an interference objective lens (10x) with a reference surface was scanned in the Z direction (thickness direction) to selectively obtain the surface roughness Ra of the outermost surface of the measurement target. If the measurement target was a film, the film to be measured was laminated to a microslide glass (Matsunami Glass Industry, product name "S200200") using static electricity to prevent foreign matter, air bubbles, and deformation lines from entering, and the surface roughness Ra was measured in accordance with JIS B 0601. <Peeling force> A sample with a width of 25 mm and a length of 50 mm was cut from the measurement object and left in an environment of 23°C and 50% relative humidity for 30 minutes or more, and then the peel force (N / 50 mm) was measured when peeled in the length direction at a peel speed of 300 mm / min and a peel angle of 180° using a universal tensile tester. The measurements were performed in an environment of 23°C and 50% relative humidity.

[0144] [Example 1] (Preparation of absorptive polarizing film) A primer composition was prepared according to U.S. Patent Application Publication No. 2020 / 0110209. The obtained primer composition was cut with a wire bar to a thickness of 60 μm and a tensile modulus of 3.5 × 10 9 The solution was applied to a TAC film (Konica Minolta, Inc., "KC2UA") having a haze of 0.9% at 200 Pa, and the coating film was dried at 60° C. for 3 minutes to form a primer layer having a thickness of 30 nm. Next, a lyotropic liquid crystalline polymer consisting of the structural unit of the above formula (1) was dissolved in water to a solid content concentration of 14% by mass. As a lyotropic liquid crystalline polymer, a birefringent aromatic polymer (Structure P1) was prepared according to Example 17 of U.S. Patent Application Publication No. 2020 / 0110209. The lyotropic liquid crystalline polymer had a sodium sulfonate base. The obtained liquid crystalline polymer aqueous solution was applied to the above primer layer with a wire bar and dried at 60 ° C. for 3 minutes to form a lyotropic liquid crystal layer with a thickness of 3 μm. Since the molecules of this material are oriented by the shear stress during coating, a retardation having a slow axis in the coating direction was expressed. Next, the organic dyes shown in the above formulas (24) to (26) were prepared in accordance with U.S. Patent Application Publication No. 2020 / 0110209. Thereafter, the organic dyes shown in the above formulas (24) to (26) were dissolved in water in a mass ratio of formula (24):formula (25):formula (26) = 18:7:8 to prepare a dyeing solution with a solid content concentration of 1.9 mass%. Next, the lyotropic liquid crystal layer was dyed by immersing it in the dyeing solution for 90 seconds, and then insolubilized by immersing it in a 10% by mass SrCl2 aqueous solution for 3 seconds. The lyotropic liquid crystal layer was then washed by immersing it in pure water for 3 seconds, and then air-dried by blowing off excess water with compressed air. In this manner, an absorptive polarizing film having a thickness of 3 μm was formed on the TAC film.

[0145] (Preparation of the first laminate) A thin film with a thickness of 30 μm and a tensile modulus of 3.0×10 was applied to the surface of the absorptive polarizing film formed on the TAC film. 8 A protective film (self-adhesive polyethylene film, manufactured by Toray Advanced Film Co., Ltd., "Tretec (registered trademark) 7832C") having a haze of 7% was attached at 100 Pa to prepare a first laminate. Then, a punching blade was used to obtain a first laminate having a rectangular shape in plan view with a long side of 350 mm and a short side of 250 mm. No scratches caused by the punching blade were found on the punched first laminate. In addition, since the first laminate does not have an adhesive layer, no glue stains caused by the adhesive were found.

[0146] (Fabrication of λ / 4 components) Polymerization was carried out using a batch polymerization apparatus consisting of two vertical reactors equipped with stirring blades and a reflux condenser controlled at 100° C. Bis[9-(2-phenoxycarbonylethyl)fluoren-9-yl]methane 29.60 parts by mass (0.046 mol), isosorbide (ISB) 29.21 parts by mass (0.200 mol), spiroglycol (SPG) 42.28 parts by mass (0.139 mol), diphenyl carbonate (DPC) 63.77 parts by mass (0.298 mol), and calcium acetate monohydrate 1.19×10 as a catalyst. -2 Part of mass (6.78×10 -5 mol) was charged. After the inside of the reactor was purged with nitrogen under reduced pressure, heating was performed with a heat medium, and stirring was started when the inside temperature reached 100 ° C. 40 minutes after the start of the temperature increase, the inside temperature was reached 220 ° C., and while controlling to maintain this temperature, the pressure was reduced and 90 minutes after reaching 220 ° C., the pressure was reduced to 13.3 kPa. Phenol vapor by-produced with the polymerization reaction was led to a reflux condenser at 100 ° C., a small amount of monomer components contained in the phenol vapor were returned to the reactor, and the uncondensed phenol vapor was led to a condenser at 45 ° C. and recovered. Nitrogen was introduced into the first reactor to restore the pressure to atmospheric pressure, and the oligomerized reaction liquid in the first reactor was transferred to the second reactor. Next, the temperature increase and pressure reduction in the second reactor were started, and the inside temperature was set to 240 ° C. and the pressure to 0.2 kPa in 50 minutes. Thereafter, polymerization was allowed to proceed until the specified stirring power was reached. When the predetermined power was reached, nitrogen was introduced into the reactor to restore pressure, and the produced polyester carbonate resin was extruded into water and the strands were cut to obtain pellets.

[0147] The obtained polyester carbonate resin (pellets) was vacuum-dried at 80°C for 5 hours, and then a long resin film having a thickness of 135μm was produced using a film-forming device equipped with a single-screw extruder (manufactured by Toshiba Machine Co., Ltd., cylinder setting temperature: 250°C), a T-die (width 200mm, setting temperature: 250°C), a chill roll (setting temperature: 120-130°C) and a winder. The obtained long resin film was stretched in the width direction at a stretching temperature of 143°C and a stretching ratio of 2.8 times to obtain a stretched film having a thickness of 48μm. The Re(550) of the obtained stretched film was 143nm, Re(450) / Re(550) was 0.86, and the Nz coefficient was 1.12.

[0148] (Preparation of the second laminate) A 5 μm-thick adhesive layer 1 was laminated on one side of the obtained λ / 4 member. A release liner 1 (polyethylene terephthalate film treated with a silicone-based release agent, thickness 38 μm, manufactured by Toray Advanced Film Co., Ltd., "#38 K Therapeel MDA") was attached to the surface of this adhesive layer 1. Next, a 15 μm thick adhesive layer 2 was laminated on the other side of the λ / 4 member. A release liner 2 (polyethylene terephthalate film (thickness 50 μm, manufactured by Mitsubishi Chemical Corporation, "Diafoil MHE50") treated with a silicone-based release agent was attached to the surface of this adhesive layer 2. In this way, a second laminate was obtained. Thereafter, a punching blade was used to obtain a second laminate having a rectangular shape in plan view with long sides of 350 mm and short sides of 250 mm.

[0149] (Preparation of Optical Laminate 1) The release liner 1 was peeled off from the second laminate punched into a rectangle to expose the pressure-sensitive adhesive layer 1. The protective film was peeled off from the first laminate punched into a rectangle, and the absorptive polarizing film of the first laminate was attached to the pressure-sensitive adhesive layer 1 of the second laminate to produce an optical laminate 1. At this time, the attachment was performed so that the absorption axis of the absorptive polarizing film of the first laminate and the slow axis of the λ / 4 member of the second laminate formed an angle of 45°. The attachment was performed so that the corners of the first laminate and the second laminate were aligned.

[0150] When the protective film was peeled off from the first laminate, no peeling failure occurred. The optical laminate 1 was produced 30 times, but the incidence of peeling failure was 0%. The peeling force of the protective film against the absorptive polarizing film was less than 0.01 N / 50 mm. In addition, when the protective film is peeled off, it appears cloudy and white, making it easy to distinguish between the base material (TAC film) and the protective film (distinguishing between the front and back), and providing excellent workability.

[0151] [Example 2] (Preparation of the first laminate) A first laminate was obtained in the same manner as in Example 1, except that a polarizing film prepared as described below was used as the absorptive polarizing film, and accordingly, a polyethylene terephthalate film was used as the substrate instead of the TAC film. Thereafter, a first laminate having a rectangular shape in plan view with a long side of 350 mm and a short side of 250 mm was obtained using a punching blade in the same manner as in Example 1. No scratches caused by the punching blade were found on the punched first laminate. In addition, since the first laminate did not have an adhesive layer, no glue stains caused by the adhesive were found.

[0152] (Preparation of absorptive polarizing film) The thermoplastic resin substrate was a long amorphous isophthalic copolymerized polyethylene terephthalate film (thickness: 100 μm) having a water absorption rate of 0.75% and a Tg of about 75° C. One side of the resin substrate was subjected to a corona treatment. A PVA aqueous solution (coating liquid) was prepared by adding 13 parts by weight of potassium iodide to 100 parts by weight of a PVA-based resin made by mixing polyvinyl alcohol (polymerization degree 4200, saponification degree 99.2 mol%) and acetoacetyl-modified PVA (manufactured by Mitsubishi Chemical Corporation, product name "GOHSENEX Z410") in a ratio of 9:1, and dissolving the mixture in water. The above PVA aqueous solution was applied to the corona-treated surface of a resin substrate and dried at 60° C. to form a PVA-based resin layer with a thickness of 13 μm, thereby producing a laminate. The obtained laminate was uniaxially stretched at its free end to 2.4 times its original size in the machine direction (longitudinal direction) between rolls with different peripheral speeds in an oven at 130° C. (auxiliary air stretching treatment). Next, the laminate was immersed in an insolubilizing bath (a boric acid aqueous solution obtained by mixing 4 parts by weight of boric acid with 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (insolubilizing treatment). Next, the film was immersed in a dye bath (an aqueous iodine solution obtained by mixing iodine and potassium iodide in a weight ratio of 1:7 with 100 parts by weight of water) at a liquid temperature of 30°C for 60 seconds while adjusting the concentration so that the single transmittance (Ts) of the final polarizing film would be 42.0% or more (dyeing process). Next, the piece was immersed in a crosslinking bath (a boric acid aqueous solution obtained by mixing 3 parts by weight of potassium iodide and 5 parts by weight of boric acid with respect to 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (crosslinking treatment). Thereafter, the laminate was immersed in an aqueous boric acid solution (boric acid concentration: 4% by weight, potassium iodide concentration: 5% by weight) at a liquid temperature of 62°C and uniaxially stretched in the longitudinal direction (longitudinal direction) between rolls with different peripheral speeds to a total stretch ratio of 5.5 times (underwater stretching treatment). Thereafter, the laminate was immersed in a cleaning bath (an aqueous solution obtained by mixing 4 parts by weight of potassium iodide with 100 parts by weight of water) at a liquid temperature of 20° C. (cleaning treatment). Thereafter, while drying in an oven maintained at 90°C, the laminate was brought into contact with a SUS heated roll whose surface temperature was maintained at 75°C for approximately 2 seconds (drying shrinkage treatment). The shrinkage rate of the laminate in the width direction due to the drying shrinkage treatment was 5.2%. In this way, the thickness was 38 μm and the tensile modulus was 2.0 × 10 9 A polarizing film (absorption type polarizing film) having a thickness of 5 μm was formed on a resin substrate having a thickness of 1 Pa.

[0153] (Preparation of Optical Laminate 1) An optical laminate 1 was obtained in the same manner as in Example 1, except that the first laminate was used. When the protective film was peeled off from the first laminate, no peeling failure occurred. As in Example 1, the optical laminate 1 was produced 30 times, but the incidence of peeling failure was 0%. The peeling force of the protective film against the absorptive polarizing film was less than 0.01 N / 50 mm. In addition, when the protective film is peeled off, it appears cloudy and white, making it easy to distinguish between the base material (polyethylene terephthalate film) and the protective film (distinguishing between the front and back), and providing excellent workability.

[0154] [Comparative Example 1] (Preparation of the first laminate) In the same manner as in Example 1, an absorptive polarizing film was formed on a TAC film, and a 5 μm-thick adhesive layer 1 was laminated on the surface of the absorptive polarizing film. A release liner 3 (polyethylene terephthalate film treated with a silicone-based release agent, thickness 38 μm, tensile modulus 2.0×10 9 Pa, Mitsubishi Chemical Polyester Film Corporation, "MRF38") was bonded to the first laminate. In this manner, a first laminate was produced. Thereafter, a punching blade was used to obtain a first laminate having a rectangular shape in plan view with long sides of 350 mm and short sides of 250 mm. No scratches caused by the punching blade were found on the punched first laminate. However, glue stains caused by the adhesive layer 1 were found on the edges. It is considered that glue stains are likely to occur significantly due to the thin thickness of the absorptive polarizing film (for example, 7 μm or less).

[0155] (Preparation of the second laminate) A self-adhesive polyethylene film (manufactured by Toray Advanced Film Co., Ltd., "Tretec (registered trademark) 7832C") was attached as a surface protection film to one side of the λ / 4 member obtained in the same manner as in Example 1. Next, a 15 μm thick adhesive layer 2 was laminated on the other side of the λ / 4 member. A release liner 2 (polyethylene terephthalate film (thickness 50 μm, manufactured by Mitsubishi Chemical Corporation, "Diafoil MHE50") treated with a silicone-based release agent was attached to the surface of this adhesive layer 2. In this way, a second laminate was obtained. Thereafter, a punching blade was used to obtain a second laminate having a rectangular shape in plan view with long sides of 350 mm and short sides of 250 mm.

[0156] (Preparation of Optical Laminate 1) The release liner 3 was peeled off from the first laminate punched into a rectangle to expose the pressure-sensitive adhesive layer 1. The surface protection film was peeled off from the second laminate punched into a rectangle, and the λ / 4 member of the second laminate was attached to the pressure-sensitive adhesive layer 1 of the first laminate to attempt to produce an optical laminate 1.

[0157] When the release liner 3 was peeled off from the first laminate punched into a rectangular shape to expose the pressure-sensitive adhesive layer 1, peeling failure occurred. Specifically, when the release liner 3 was peeled off from the first laminate having a very thin absorptive polarizing film, peeling occurred between the TAC film and the absorptive polarizing film. Thirty attempts were made to produce the optical laminate 1, and the occurrence rate of peeling failure was 100%. The peeling force of the release liner 3 against the pressure-sensitive adhesive layer 1 was 0.07 N / 50 mm to 0.15 N / 50 mm.

[0158] [Comparative Example 2] (Preparation of the first laminate) The protective film was a PET film (total thickness 48 μm, tensile modulus 2.0 × 10 9 A first laminate was obtained in the same manner as in Example 1, except that a mask made of "E-MASK RP109F" (manufactured by Nitto Denko Corporation, Pa, haze 3.0%) was used. Thereafter, a first laminate having a rectangular shape in plan view with a long side of 350 mm and a short side of 250 mm was obtained using a punching blade in the same manner as in Example 1. No scratches caused by the punching blade were found on the punched first laminate. In addition, no glue stains caused by the adhesive were found on the punched first laminate.

[0159] (Preparation of Optical Laminate 1) An attempt was made to prepare an optical laminate 1 in the same manner as in Example 1, except that the first laminate was used. However, when peeling the protective film from the first laminate, peeling failure occurred. Specifically, when peeling the protective film from the absorptive polarizing film, peeling occurred between the TAC film and the absorptive polarizing film. The preparation of the optical laminate 1 was attempted 30 times, and the occurrence rate of peeling failure was 90%. The peeling force of the protective film against the absorptive polarizing film was 0.01 N / 50 mm.

[0160] In Comparative Examples 1 and 2, when laminating the absorptive polarizing film and the λ / 4 member, poor peeling of the release liner or protective film occurred, and it was almost impossible to proceed to the next step. On the other hand, in Examples 1 and 2, when the absorptive polarizing film and the λ / 4 member were laminated, no peeling failure of the protective film occurred, and the next step could be proceeded to. Specifically, the substrate (TAC film or polyethylene terephthalate film) was peeled off from the absorptive polarizing film of the optical laminate 1. The peeling force of the substrate to the absorptive polarizing film was less than 0.01 N / 50 mm in both Examples 1 and 2. Then, a reflective polarizing film ("APCF" manufactured by Nitto Denko Corporation) was bonded to the absorptive polarizing film via a 10 μm thick adhesive layer. Next, a protective member prepared as described below was bonded to the absorptive polarizing film via a 12 μm thick adhesive layer to obtain an optical laminate.

[0161] (Creating protective materials) The following hard coat layer forming material was applied to an acrylic film (thickness 40 μm) having a lactone ring structure and heated at 90° C. for 1 minute. After heating, the coating layer was irradiated with a high-pressure mercury lamp with an integrated light intensity of 300 mJ / cm. 2 The coating layer was cured by irradiation with ultraviolet light of 1000 .mu.m to prepare an acrylic film (thickness 44 .mu.m) on which a hard coat layer with a thickness of 4 .mu.m was formed. Next, the following coating solution A for forming an anti-reflection layer was applied onto the hard coat layer using a wire bar, and the applied coating solution was heated at 80°C for 1 minute and dried to form a coating film. The dried coating film was then irradiated with a high-pressure mercury lamp with an integrated light quantity of 300 mJ / cm2. 2 The coating was cured by irradiation with ultraviolet light of 1500 nm to form an antireflection layer A having a thickness of 140 nm. Next, the following coating solution B for forming an antireflection layer was applied onto the antireflection layer A using a wire bar, and the applied coating solution was heated at 80°C for 1 minute and dried to form a coating film. The dried coating film was irradiated with a high-pressure mercury lamp with an integrated light amount of 300 mJ / cm 2 The coating was cured by irradiation with ultraviolet light of 1000 ohms to form an antireflection layer B having a thickness of 105 nm. In this way, a protective member (thickness: 44 μm) was obtained.

[0162] (Hard Coat Layer Forming Material) A hard coat layer forming material was prepared by mixing 50 parts of a urethane acrylic oligomer (manufactured by Shin-Nakamura Chemical Co., Ltd., "NK Oligo UA-53H"), 30 parts of a multifunctional acrylate mainly composed of pentaerythritol triacrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd., product name "Viscoat #300"), 20 parts of 4-hydroxybutyl acrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd.), 1 part of a leveling agent (manufactured by DIC Corporation, "GRANDIC PC4100") and 3 parts of a photopolymerization initiator (manufactured by Ciba Japan, "Irgacure 907") and diluting with methyl isobutyl ketone to a solids concentration of 50%.

[0163] (Anti-reflection layer forming coating solution A) 100 parts by weight of a multifunctional acrylate (manufactured by Arakawa Chemical Industries, Ltd., product name "Opstar KZ6728", solid content 20% by weight), 3 parts by weight of a leveling agent (manufactured by DIC Corporation, "GRANDIC PC4100"), and 3 parts by weight of a photopolymerization initiator (manufactured by BASF, product name "OMNIRAD907", solid content 100% by weight) were mixed. The mixture was diluted with butyl acetate as a diluting solvent to a solid content of 12% by weight, and the mixture was stirred to prepare coating solution A for forming an anti-reflection layer.

[0164] (Anti-reflection layer forming coating solution B) 100 parts by weight of a polyfunctional acrylate mainly composed of pentaerythritol triacrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd., trade name "Viscoat #300", solid content 100% by weight), 150 parts by weight of hollow nanosilica particles (manufactured by JGC Catalysts and Chemicals Co., Ltd., trade name "Surulia 5320", solid content 20% by weight, weight average particle diameter 75 nm), 50 parts by weight of solid nanosilica particles (manufactured by Nissan Chemical Industries, Ltd., trade name "MEK-2140Z-AC", solid content 30% by weight, weight average particle diameter 10 nm), 12 parts by weight of a fluorine-containing additive (manufactured by Shin-Etsu Chemical Co., Ltd., trade name "KY-1203", solid content 20% by weight), and 3 parts by weight of a photopolymerization initiator (manufactured by BASF, trade name "OMNIRAD907", solid content 100% by weight) were mixed. To the mixture was added a mixed solvent of TBA (tertiary butyl alcohol), MIBK (methyl isobutyl ketone) and PMA (propylene glycol monomethyl ether acetate) in a weight ratio of 60:25:15 as a dilution solvent until the total solids content was 4% by weight, and the mixture was stirred to prepare coating solution B for forming an anti-reflection layer.

[0165] The present invention is not limited to the above-described embodiment, and various modifications are possible. For example, the above-described embodiment may be replaced with a configuration that is substantially the same as the configuration shown in the above-described embodiment, a configuration that provides the same effect, or a configuration that can achieve the same purpose. [Industrial Applicability]

[0166] The optical laminate according to the embodiment of the present invention can be used for a display such as VR goggles. [Explanation of symbols]

[0167] 1 optical laminate, 10 display system, 12 display element, 14 reflective polarizing member, 16 first lens portion, 18 half mirror, 20 first λ / 4 member, 22 second λ / 4 member, 24 second lens portion, 26 user's eye, 28 absorptive polarizing member, 30 third λ / 4 member, 31 protective member, 41 first adhesive layer, 42 second adhesive layer, 43 adhesive layer, 44 adhesive layer, 51 surface protective film, 52 release liner, 53 substrate, 54 protective film, 100 first laminate, 200 second laminate.

Claims

1. Preparing a first laminate including a substrate, an absorptive polarizing film formed on the substrate, and a protective film bonded to the absorptive polarizing film; cutting the first laminate into a predetermined shape to obtain a sheet-like first laminate; Preparing a sheet-like second laminate having a phase difference member having a first main surface and a second main surface facing each other, and a first pressure-sensitive adhesive layer disposed on the first main surface side of the phase difference member; and peeling off the protective film from the sheet-like first laminate, and bonding the absorptive polarizing film of the sheet-like first laminate to the first pressure-sensitive adhesive layer of the sheet-like second laminate, The thickness of the absorptive polarizing film is 7 μm or less, The tensile modulus of the protective film is smaller than the tensile modulus of the base material. A method for producing an optical laminate.

2. The tensile modulus of the protective film is 1.0×10 9 The method of claim 1, wherein the viscosity is less than 100 Pa.

3. The method according to claim 1 , wherein a peel strength of the protective film to the absorptive polarizing film is less than 0.01 N / 50 mm.

4. The method according to claim 1 , wherein the protective film is a self-adhesive film.

5. The method according to claim 1 , wherein the protective film has a haze of 3% or more.

6. The method according to claim 1 , further comprising the steps of: laminating the absorptive polarizing film to the first pressure-sensitive adhesive layer; and peeling the substrate from the absorptive polarizing film.

7. The manufacturing method according to claim 1 , wherein the sheet-like second laminate has the same shape in a plan view as the first laminate after the cutting.

8. The method according to claim 1 , wherein the second laminate has a second pressure-sensitive adhesive layer disposed on the second main surface side of the retardation member.

9. The method according to claim 8 , wherein the second pressure-sensitive adhesive layer has a thickness greater than a thickness of the first pressure-sensitive adhesive layer.

Citation Information

Patent Citations

  • Surface protection film

    JP2001004802A

  • Transfer body for circular polarizing plate, circular polarizing plate, image display unit, manufacturing method of transfer body for circular polarizing plate and manufacturing method of circular polarizing plate

    JP2014123068A

  • Polarizer

    JP2017009908A

  • Polarizer protection film

    JP2018084615A

  • Method for manufacturing optical laminate and method for manufacturing image display device

    JP2018120120A